Crosslinked zwitterionic polymer networks and their use in membrane filters
Patent Information
- Application Number
- JP2023564469
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-22
- Filing Date
- 2022-04-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Membrane filtration processes are severely affected by fouling, leading to decreased performance and increased costs due to adsorption and accumulation of feed components on the membrane surface, which necessitates frequent cleaning and maintenance.
Development of crosslinked copolymer networks with tunable size-based selectivity using zwitterionic repeat units and hydrophobic repeat units, crosslinked via thiol-ene click chemistry to form membranes with improved chemical and mechanical stability, allowing for precise control of pore size and enhanced resistance to fouling.
The crosslinked membranes exhibit high rejection rates for small molecules and ions, maintain flux under fouling conditions, and demonstrate rapid scalability and chemical stability, reducing operational costs and improving efficiency in water purification and separation processes.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims the benefit of priority to U.S. Provisional Application No. 63 / 178,072, filed April 22, 2021, the contents of which are incorporated by reference. GOVERNMENT SUPPORT
[0002] This invention was made with United States Government support under Grant No. DE-FE0031851 awarded by the United States Department of Energy and Grant No. 1553661 awarded by the National Science Foundation. The United States Government has certain rights in the invention. [Background technology]
[0003] Membrane filtration is an important and promising method for water purification, reclamation and reuse. Membranes with various pore sizes can be used for a wide range of purposes, from simply removing pathogenic microorganisms to desalination by reverse osmosis (RO). Membranes also serve as an efficient, simple and scalable separation method in various industries such as food, beverage, dairy, and bio / pharmaceutical industries.
[0004] Membranes with improved selectivity or the ability to separate solutes with better precision could result in improved economic viability and energy efficiency of several other processes. For example, membranes with improved selectivity between sulfate and chloride anions could change the composition of seawater and wastewater for use as drilling fluids in offshore oil wells while operating at lower applied pressures. Membranes with extremely small pore sizes but low salt rejection could result in greatly improved effluent quality for difficult wastewater streams, especially those with high organic content such as those from the food industry.
[0005] All of the above mentioned membrane processes are often severely affected by fouling, defined as the degradation of membrane performance due to adsorption and accumulation of feed components on the membrane surface. It is common for membrane permeability to decrease significantly and membrane selectivity to change. Fouling management is a significant component of the costs associated with membrane systems and requires increased energy usage, downtime, maintenance and regular cleaning involving chemical use, and more complex processes. Summary of the Invention [Means for solving the problem]
[0006] Provided herein are cross-linked copolymer networks designed to create membranes with tunable size-based selectivity for small organic molecules and selectivity between dissolved ions.
[0007] In one embodiment, a crosslinked copolymer network comprising: a copolymer comprising a plurality of zwitterionic repeat units and a plurality of a first type of hydrophobic repeat units; A plurality of crosslinking units; and Multiple crosslinks wherein each crosslinking unit comprises a first terminal thiol moiety and a second terminal thiol moiety; each hydrophobic repeating unit comprises an alkene; and each crosslink is formed from (i) the first terminal thiol moiety of the crosslinking unit and the alkene of the first hydrophobic repeating unit, and (ii) the second terminal thiol moiety of the crosslinking unit and the alkene of the second hydrophobic repeating unit.
[0008] In one aspect, a thin film composite membrane is disclosed that includes a porous substrate and a selective layer that includes a crosslinked copolymer network as disclosed herein, where the average effective pore size of the porous substrate is larger than the average effective pore size of the selective layer, and the selective layer is disposed on a surface of the porous substrate.
[0009] In one aspect, there is provided a method of making a crosslinked copolymer network as disclosed herein, comprising: providing a copolymer comprising a plurality of zwitterionic repeat units and a plurality of a first type of hydrophobic repeat units, each hydrophobic repeat unit comprising an alkene; providing a plurality of cross-linking units, each cross-linking unit comprising a first terminal thiol moiety and a second terminal thiol moiety; providing a photoinitiator; mixing the copolymer, the plurality of crosslinking units, and a photoinitiator, thereby forming a mixture; irradiating the mixture with UV light, thereby forming a cross-linked copolymer. A method is disclosed that includes: [Brief description of the drawings]
[0010] [Figure 1A] Schematic of molecular self-assembly to generate a bicontinuous network of zwitterionic (indicated by positively (+) and negatively (-) charged groups) and bridging hydrophobic (circle with stripes) domains. Water and smaller solutes can pass through the zwitterionic channel, while larger solutes are retained. [Figure 1B] FIG. 1 shows the synthesis scheme of crosslinkable zwitterionic random copolymer (ZAC) and its crosslinking reaction via thiol-ene click chemistry. [Figure 1C] FIG. 1 shows the synthesis scheme of crosslinkable zwitterionic random copolymer (ZAC) and its crosslinking reaction via thiol-ene click chemistry. [Figure 1D] NMR spectrum of structure-PAM-r-SBMA showing copolymerization. [Figure 1E] 1 is an IR spectrum of structure-PAM-r-SBMA showing copolymerization. [Figure 1F]FIG. 2 is a schematic diagram of related UV assisted cross-linking. [Figure 2A] Shown is an SEM image of an uncoated PS-35 support membrane at 7000x magnification. [Figure 2B] Shown is an SEM image of an uncrosslinked (TCZ-0) membrane with a random zwitterionic supporting layer at 7000x magnification. [Figure 2C] SEM image of crosslinked (TCZ-40) membrane after immersion in TFE for 24 hours at 7000x magnification. Crosslinking prevented the selective layer from dissolving in TFE, a solvent that readily dissolves the uncrosslinked copolymer. [Figure 3A] NMR spectrum of Structure-P(AM-r-TFEMA-r-MPC) showing copolymerization. [Figure 3B] IR spectrum of Structure-P(AM-r-TFEMA-r-MPC) showing copolymerization. [Figure 4] The rejection rates of anionic dyes of different molecular diameters are shown. [Diagram 5] The rejection rates of anionic dyes of different molecular diameters are shown. [Figure 6] Figure 1 shows the size-based small molecule separation capacity of the TCZ-40 membrane monitored when two different dyes (0.05 mM each), Chicago sky blue 6B (0.88 nm) and methyl orange (0.79 nm), were mixed as the feed for diafiltration experiments. [Figure 7A] 1 is a graph of rejection (%) versus diameter (nm) showing the rejection of various sizes of anionic dyes by TERP-C-0 (uncrosslinked) and TERP-C-14 (crosslinked) membranes. Both membranes exhibited a sharp size cutoff. The crosslinked membrane exhibited higher rejection than the uncrosslinked membrane, confirming that crosslinking results in a smaller effective pore size. [Figure 7B] 1 is a graph of rejection (%) versus diameter (nm) showing the rejection performance of TERP-C-14. [Figure 7C]Figure 1 is a graph of absorbance vs. wavelength (nm) showing the fractionation of two dyes, Chicago Sky Blue 6B (0.88 nm) and Methyl Orange (0.79 nm), by TERP-C-14, with UV spectra of the feed, permeate, and each dye recorded for reference. Only Methyl Orange permeated the TERP-C-14 membrane, while Chicago Sky Blue 6B was fully retained. [Figure 8A] 1 shows the rejection performance of 20 mM NaCl salt at various applied pressures for uncrosslinked TCZ-0 and crosslinked TCZ membranes. [Figure 8A] 1 shows the rejection performance of 20 mM Na2SO4 salt at various applied pressures for uncrosslinked TCZ-0 and crosslinked TCZ membranes. [Figure 8A] 1 shows the rejection performance of 20 mM MgSO4 salt at various applied pressures for uncrosslinked TCZ-0 and crosslinked TCZ membranes. [Figure 9A] 1 shows the rejection of 20 mM Na2SO4 at various applied pressures for a crosslinked TERP membrane. [Figure 9B] 1 shows the rejection of 20 mM NaCl at various applied pressures for a crosslinked TERP membrane. [Figure 10A] 1 shows dead-end filtration of a contaminant solution through TCZ-30. [Figure 10B] 1 shows dead-end filtration of a contaminant solution through TCZ-40. [Figure 10C] 1 shows dead-end filtration of a pollutant solution through a commercial membrane, NP-30. [Figure 11A] 1 shows dead-end filtration of a contaminant solution through TCZ-40. [Figure 11B] 1 shows dead-end filtration of a pollutant solution through a commercial membrane, NP-30. [Figure 12A]Figure 1 is a graph of J / J0 versus time (hours (hr)) showing dead-end fouling data in an oil-in-water emulsion solution for the commercial membrane NP-30. The plot shows the change in normalized flux, defined as the ratio of the flux (or permeate flux) (J) at a given time point normalized by the initial pure water flux (Jo). After stabilization of the initial water flux (blue), the normalized flux during filtration of the foulant solution is monitored (circles). The membrane is then rinsed several times with water and the normalized water flux is measured again (cones). [Figure 12B] Data for TERP-C-14 is shown. The TERP-C-14 membrane shows no flux loss during and after exposure to the pollutant solution, whereas the commercial membrane shows significant (about 48%) irreversible flux loss. The pollutant solution consisted of a 1500 mg / L oil-in-water (9:1) emulsion. For all membranes, Jo=2.75 Lm-2hr-1. [Figure 13A] FIG. 1 is a graph of J / J0 versus time (hr) showing fouling of commercial membrane NP-30 by 1 g / L bovine serum albumin in 10 mM CaCl2 solution. [Figure 13B] Data for the TERP-C-14 membrane with 1 g / L bovine serum albumin in 10 mM CaCl2 solution are shown. The TERP-C-14 membrane showed no flux loss during and after exposure to the pollutant solution, whereas the commercial NP-30 membrane showed a significant (about 27%) irreversible flux loss. Jo=2.75 Lm-2 hr-1. [Figure 14A] SEM cross-sectional image of uncoated PS-35 support membrane after immersion in TFE for 24 hours, magnification 7000x. [Figure 14B] SEM cross-sectional image of the as-cast uncrosslinked (TERP-C-0) membrane after immersion in TFE for 24 hours, magnification 7000x. [Figure 14C] FIG. 14 is a cross-sectional SEM image of a cross-linked TERP-C-14 membrane after immersion in TFE for 24 hours, showing that cross-linking prevented the selective layer from dissolving in TFE, a solvent that readily dissolves the uncross-linked copolymer. Magnification 7000x. [Figure 15] 1 is a graph of permeance decrease (%) versus crosslinking time (min) showing the effect of crosslinking time on membrane permeance decrease. [Figure 16] The polymers, crosslinkers, and photoinitiators used in Examples 17 to 20 are shown below. [Figure 17] Bright-field TEM image of the self-assembled nanostructures of P(AM-r-SBMA). The zwitterionic domains are positively stained with Cu ions and appear dark. The inset shows the fast Fourier transform of the image. [Figure 18] FIG. 1 shows the ATR-FTIR spectra of uncrosslinked (TCZ-0) and crosslinked (TCZ-40) films of the random zwitterionic copolymer P(AM-r-SBMA). [Figure 19A] 1 shows the XPS spectra of TCZ-0 and TCZ-40 films. 1 shows the survey scan. [Figure 19B] XPS spectra of TCZ-0 and TCZ-40 films are shown. High-resolution spectra of the S2p region are shown. [Figure 20] 1 shows the effect of crosslinking time on the decrease in membrane permeance. [Figure 21A] Figure 1 shows fouling of the TCZ-30 membrane with 1 g / L BSA in PBS, as demonstrated by the change in normalized water flux during filtration of the contaminant (circles) and after rinsing with water (triangles and squares). The fouling is negligible for both the TCZ-30 and TCZ-40 membranes. [Figure 21B] Figure 1 shows fouling of the TCZ-40 membrane with 1 g / L BSA in PBS, as demonstrated by the change in normalized water flux during filtration of the contaminant (circles) and after rinsing with water (triangles and squares). Fouling is negligible for both TCZ-30 and TCZ-40 membranes. [Figure 22] Figure 1 shows a comparison of pure water permeance of membrane TCZ-20 before and after acid / base treatment. The membrane was immersed in 0.5M NaOH and HCl respectively, after which the pure water permeance was recorded and the data was compared with untreated TCZ-20. [Figure 23]Protein stained images of commercial NP-30 and TCZ-40 membranes are shown. NP-30 showed more protein adsorption than our TCZ-40 membrane. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Chemical modification of zwitterion-containing amphiphilic copolymers, particularly in the form of membrane selective layers, using thiol-ene click chemistry to tailor effective pore size, improve chemical, thermal and mechanical stability, and incorporate additional functional groups is disclosed.
[0012] One embodiment of the click crosslinking reaction can be represented by thiol (R-SH) + alkene (CH2=CH-) -> RS-CH2-CH2-. In this representation, once formed, the crosslink does not contain either a thiol group or an alkene; it is their reaction product. In other words, a dithiol-containing compound can be considered as a crosslinking reagent that forms crosslinks that are part of a crosslinked copolymer network by reaction of its constituent thiols with the alkenes of at least two hydrophobic repeat units.
[0013] The present invention utilizes specifically designed random zwitterionic copolymers (rZACs) that contain at least two types of repeat units: - Zwitterionic repeating units (i.e., moieties carrying an equal number of positively and negatively charged groups) - Hydrophobic repeat units containing alkene groups (eg allyl methacrylate).
[0014] The materials can also contain additional hydrophobic repeat units that are not crosslinkable. rZACs prepared by various combinations of hydrophobic repeat units (or hydrophobic monomers) and zwitterionic repeat units (or hydrophilic zwitterionic monomers) microphase separate to form a classic bicontinuous network of hydrophobic and zwitterionic domains over a wide composition range. Hydrophilic zwitterionic nanodomains form as a network composed of zwitterionic nanochannels for the permeation of water and solutes small enough to penetrate, connected by the hydrophobic domains of the copolymer (Figure 1A).
[0015] These copolymers are synthesized by methods known in the art of polymer chemistry, such as atom transfer radical polymerization (ATRP) or radical addition fragmentation chain transfer (RAFT) polymerization. The invention involves forming the rZAC into a thin film composite (TFC) membrane or thin film. The thin film is prepared by forming the rZAC into a desired shape (e.g., a free-standing thin film or TFC membrane, including an rZAC membrane covering a porous support); exposing the rZAC to multiple crosslinking units as well as a photoinitiator (each crosslinking unit containing at least two terminal thiol moieties, e.g., thiols or dithiols); and irradiating the film with UV light, which results in a reaction between the thiol groups and the alkene groups of the hydrophobic repeat units of the copolymer (Figure 1B). This reaction, called the thiol-ene click reaction, can be used to attach desired functional groups to the rZAC. In a preferred embodiment, a dithiol is used and the reaction results in crosslinking of the copolymer. Thiol-ene "click" chemistry is characterized by very high reaction rates, high conversions, and selective yields. These features make it a good option for post-functionalization of membranes in roll-to-roll systems where short residence times are required with high yields. The reaction mechanism of this reaction allows reliable incorporation of a wide range of functionalities at a time scale that is aligned with the production speed of the membranes. The reported time scale of the thiol-ene click reaction constitutes a major bottleneck for roll-to-roll manufacturing and scale-up. The use of the rapid thiol-ene click reaction to achieve effective crosslinking of self-assembled membranes in seconds to precisely tune the pore diameter is disclosed.
[0016] The use of rZAC as a selective layer in a composite filtration membrane is also disclosed. In one embodiment, rZAC is coated onto a porous support by methods well understood in the membrane industry (e.g., doctor blade coating, spray coating). Upon deposition, the zwitterionic groups are expected to self-assemble to generate microphase-separated domains or zwitterionic clusters. The rZAC layer is then crosslinked using a click reaction with a crosslinking reagent having at least two thiol groups (e.g., dithiol, tetrathiol), resulting in crosslinking. This crosslinking results in improved thermal and chemical stability. Importantly and unusually, the crosslinking results in a change in the effective pore size of the membrane, as small as about 1 nm, allowing selectivity between small molecules and between salt ions. An important and unexpected feature of this reaction is that a high degree of crosslinking and large changes in membrane selectivity can be achieved with only about 5-40 seconds of UV exposure. Such a short timescale is important for the scalability of the present technology and is significantly shorter than the timescales reported for other click-based modification methods for membranes. Finally, the resulting membranes are extremely resistant to fouling, enhancing their usefulness in many areas, such as water desalination and softening, removal of metal ions and organic contaminants from water, separation of organic molecules dissolved in water, and wastewater treatment, including treatment of difficult wastewater streams.
[0017] In one embodiment, a crosslinked copolymer network is disclosed that includes a copolymer comprising a plurality of zwitterionic repeat units and a plurality of hydrophobic repeat units of a first type; a plurality of crosslinking units; and a plurality of crosslinks; each crosslinking unit includes a first terminal thiol moiety and a second terminal thiol moiety; each hydrophobic repeat unit includes an alkene; each crosslink is formed from (i) the first terminal thiol moiety of the crosslinking unit and the alkene of the first hydrophobic repeat unit, and (ii) the second terminal thiol moiety of the crosslinking unit and the alkene of the second hydrophobic repeat unit. In other words, in the crosslinked copolymer network formed, each crosslinking unit includes a first terminal thioether moiety and a second terminal thioether moiety; each crosslink is formed from (i) the first terminal thiol moiety of the crosslinking reagent reacted with the alkene of the first hydrophobic repeat unit, and (i) the second terminal thiol moiety of the crosslinking reagent reacted with the alkene of the second hydrophobic repeat unit.
[0018] In certain embodiments, each of the zwitterionic repeat units independently comprises sulfobetaine, carboxybetaine, phosphorylcholine, imidazolium alkylsulfonate, or pyridinium alkylsulfonate. In certain embodiments, each of the zwitterionic repeat units independently comprises sulfobetaine acrylate, sulfobetaine acrylamide, carboxybetaine acrylate, carboxybetaine methacrylate, 2-methacryloyloxyethyl phosphorylcholine, acryloxy phosphorylcholine, phosphorylcholine acrylamide, phosphorylcholine methacrylamide, carboxybetaine acrylamide, 3-(2-vinylpyridinium-l-yl)propane-1-sulfonate, 3-(4-vinylpyridinium-l-yl)propane-l-sulfonate, or sulfobetaine methacrylate.
[0019] In certain embodiments, each of the hydrophobic repeat units is independently formed from styrene, alkyl acrylates, alkyl methacrylates, alkyl acrylamides, acrylonitriles, aryl acrylates, aryl methacrylates, and aryl acrylamides.
[0020] In certain embodiments, the copolymer is poly((allyl methacrylate)-random-(sulfobetaine methacrylate)), or poly((allyl methacrylate)-random-(2-methacryloyloxyethyl phosphorylcholine)).
[0021] In certain embodiments, the crosslinked copolymer network further comprises a plurality of second type hydrophobic repeat units, each of which is independently formed from an alkyl acrylate, an alkyl methacrylate, an alkyl acrylamide, an acrylonitrile, an aryl acrylate, an aryl methacrylate, and an aryl acrylamide. In certain embodiments, the second type hydrophobic repeat unit is formed from 2,2,2-trifluoroethyl methacrylate.
[0022] In certain embodiments, the hydrophobic repeat units comprise carbon-carbon double bonds (alkenes). In certain embodiments, the crosslinkable moieties comprise allyl (CH2-CH=CH2), vinyl (-CH=CH2 or -CH=CH-), vinyl ether (-O-CH=CH2), or vinyl ester (-CO-O-CH=CH2).
[0023] In certain embodiments, the copolymer is poly(allyl methacrylate-random-trifluoroethyl methacrylate-random-2-methacryloyloxyethyl phosphorylcholine). In certain embodiments, the copolymer has a molecular weight of about 3,000 to about 10,000,000 daltons, about 5,000 to about 9,000,000 daltons, about 10,000 to about 8,000,000 daltons, about 20,000 to about 7,000,000 daltons, or about 10,000 to about 10,000,000 daltons. For example, about 20,000 to about 9,000,000 daltons, about 30,000 to about 8,000,000 daltons, about 40,000 to about 7,000,000 daltons, about 50,000 to about 6,000,000 daltons, about 60,000 to about 5,000,000 daltons, about 70,000 to about 4,000,000 daltons, about 80,000 to about 3,000,000 daltons, about 90,000 to about 2,000,000 daltons, about 100,000 to about 1,000,000 daltons, 0 daltons, about 20,000 to about 900,000 daltons, about 20,000 to about 800,000 daltons, about 20,000 to about 700,000 daltons, about 20,000 to about 600,000 daltons, about 20,000 to about 500,000 daltons, about 20,000 to about 400,000 daltons, about 20,000 to about 300,000 daltons, about 20,000 to about 200,000 daltons, or about 20,000 to about 100,000 daltons. In certain embodiments, the copolymer has a molecular weight of about 20,000 to about 500,000 daltons.
[0024] In certain embodiments, the zwitterionic repeat units and the hydrophobic repeat units each comprise 20-80% by weight of the copolymer, hi certain embodiments, the zwitterionic repeat units comprise 25-75% by weight of the copolymer and the hydrophobic repeat units comprise 25-75% by weight of the copolymer.
[0025] In certain embodiments, the copolymer is poly((allyl methacrylate)-random-(sulfobetaine methacrylate)), the zwitterionic repeat units constitute 25-75% by weight of the copolymer, and the copolymer has a molecular weight of about 20,000 to about 100,000 daltons.
[0026] In certain embodiments, the copolymer is poly((allyl methacrylate)-random-(trifluoroethyl methacrylate)-random-(sulfobetaine methacrylate)), the zwitterionic repeat units constitute 25 to 75% by weight of the copolymer, and the copolymer has a molecular weight of about 20,000 to about 100,000 daltons.
[0027] In certain embodiments, the copolymer is poly((allyl methacrylate)-random-(trifluoroethyl methacrylate)-random-(methacryloxyphosphorylcholine)), the zwitterionic repeat units constitute 25 to 75% by weight of the copolymer, and the copolymer has a molecular weight of about 20,000 to about 100,000 daltons.
[0028] In certain embodiments, the multiple bridging units are represented by FG-CL-FG, where FG is a linker-thiol moiety and CL is a C1-C 20 Divalent aliphatic radicals, C1-C 20 A divalent heteroaliphatic radical, a divalent aryl radical, or a divalent heteroaryl radical. In certain embodiments, CL is a C1-C 20 Divalent aliphatic radical or C1-C 20 A divalent heteroaliphatic radical. In certain embodiments, FG-CL-FG is -S-(CH2)6-S-, or -S-(CH2)2-O-(CH2)2-O-(CH2)2-S-.
[0029] In yet another aspect, a thin film composite membrane is disclosed comprising a porous substrate and a selective layer comprising a crosslinked copolymer network as disclosed herein, wherein the average effective pore size of the porous substrate is larger than the average effective pore size of the selective layer; and the selective layer is disposed on a surface of the porous substrate.
[0030] In some embodiments, the selective layer has an average effective pore size of about 0.1 nm to about 2.0 nm. For example, the selective layer has an average effective pore size of about 0.1 nm to about 1.8 nm, about 0.1 nm to about 1.6 nm, about 0.1 nm to about 1.4 nm, about 0.1 nm to about 1.2 nm, about 0.1 nm to about 1.0 nm, about 0.1 nm to about 0.8, about 0.1 nm to about 0.6 nm, about 0.1 nm to about 0.4 nm, about 0.1 nm to about 0.2 nm, about 0.3 nm to about 2.0 nm, about 0.5 nm to about 2.0 nm, about 0.7 nm to about 2.0 nm, about 0.7 nm to about 1.2 nm, about 0.9 nm to about 2.0 nm, or about 1 nm to about 2.0 nm. In some embodiments, the selective layer has an average effective pore size of about 0.1 nm to about 1.2 nm. In one embodiment, the selective layer has an average effective pore size of about 0.7 nm to about 1.2 nm.
[0031] In one embodiment, the selective layer has a thickness of about 10 nm to about 10 μm. For example, the selective layer has a thickness of about 20 nm to about 9 μm, about 30 nm to about 8 μm, about 40 nm to about 7 μm, about 50 nm to about 6 μm, about 60 nm to about 5 μm, about 70 nm to about 4 μm, about 80 nm to about 3 μm, about 90 nm to about 2 μm, or about 100 nm to about 1 μm. In one embodiment, the selective layer has a thickness of about 100 nm to about 2 μm.
[0032] In some embodiments, the thin film composite membrane rejects charged solutes and salts. In some embodiments, the selective layer rejects more than 95% of sulfate ions (SO 2- In one embodiment, the selective layer exhibits a rejection rate of less than 35% of chloride ions (Cl - In certain embodiments, the selective layer has a rejection rate of more than 50 sulfate ions (SO 2- ) / Chloride ion (C1 -) separation factor. In a particular embodiment, the selective layer has a separation factor of about 75 sulfate ions (SO 2- ) / Chloride ion (C1 - ) indicates the separation factor.
[0033] In certain embodiments, the selective layer exhibits different anion rejection for salts having the same cation, hi some embodiments, the selective layer exhibits different anion rejection for salts selected from NaF, NaCl, NaBr, NaI, Na2SO4, and NaClO4, and in some embodiments, the selective layer exhibits different rejection for different anionic dyes.
[0034] In certain embodiments, the selective layer exhibits a Chicago Sky Blue 6B / Methyl Orange separation factor of about 10.
[0035] In certain embodiments, the selective layer exhibits greater than about 95% rejection of vitamin B 12. In certain embodiments, the selective layer exhibits greater than about 35% rejection of riboflavin.
[0036] In certain embodiments, the selective layer exhibits anti-fouling properties. In certain embodiments, the selective layer exhibits resistance to fouling by oil emulsions. In certain embodiments, the selective layer exhibits resistance to fouling by bovine serum albumin solutions. In some embodiments, the selective layer is stable when exposed to chlorine bleach. In certain embodiments, the selective layer exhibits size-based selectivity between uncharged organic molecules. In some embodiments, the selective layer exhibits >95% or >99% rejection for neutral molecules having a hydrated diameter of about 1.5 nm or greater.
[0037] In yet another aspect, a method of making a crosslinked copolymer network as disclosed herein is disclosed, the method including providing a copolymer comprising a plurality of zwitterionic repeat units and a plurality of a first type of hydrophobic repeat units, where each hydrophobic repeat unit comprises an alkene, and providing a plurality of crosslinking units, where each crosslinking unit comprises a first terminal thiol moiety and a second terminal thiol moiety; providing a photoinitiator, and mixing the copolymer, the plurality of crosslinking units, and the photoinitiator, thereby forming a mixture; and irradiating the mixture with UV light, thereby forming a crosslinked copolymer.
[0038] In certain embodiments, the mixture further comprises a solvent. In certain embodiments, the solvent is a mixture of isopropanol and hexane. In certain embodiments, the irradiation is carried out at room temperature. In certain embodiments, the photoinitiator is 2-phenylacetophenone.
[0039] In certain embodiments, irradiation is performed for about 10 seconds to about 20 minutes. In certain embodiments, irradiation is performed for about 30 seconds. In certain embodiments, irradiation is performed for about 60 seconds. In certain embodiments, irradiation is performed for about 90 seconds. In certain embodiments, irradiation is performed for about 120 seconds.
[0040] In yet another aspect, a method of pharmaceutical production is disclosed comprising contacting a thin film composite membrane as disclosed herein with a mixture containing one or more pharmaceutical compounds; and separating the one or more pharmaceutical compounds via size-selective filtration.
[0041] In yet another aspect, a method of textile dyeing and finishing is disclosed that includes contacting a thin film composite membrane disclosed herein with a mixture containing one or more textile dyes; and separating the one or more textile dyes via size selective filtration.
[0042] In yet another aspect, a method of buffer exchange is disclosed, comprising contacting a thin film composite membrane disclosed herein with a first buffer solution; and replacing the first buffer solution with a second buffer solution.
[0043] In yet another aspect, a method for purifying a peptide is disclosed, the method comprising contacting a thin film composite membrane disclosed herein with a mixture containing one or more peptides; and separating the one or more peptides via size-selective filtration.
[0044] In yet another aspect, a method for removing divalent ions from water is disclosed, the method comprising contacting a thin film composite membrane disclosed herein with an aqueous mixture containing divalent ions; and removing some or all of the divalent ions from the aqueous mixture via size selective filtration.
[0045] In yet another aspect, a method for removing organic solutes from water is disclosed, the method comprising contacting a thin film composite membrane disclosed herein with an aqueous solution containing the organic solutes; and separating the organic solutes by size selective filtration.
[0046] In yet another aspect, a method for removing disease-causing microorganisms is disclosed, the method comprising contacting a thin film composite membrane as disclosed herein with a mixture containing one or more pathogenic microorganisms; and separating the one or more pathogenic microorganisms via reverse osmosis.
[0047] In yet another aspect, a method of size-selective separation is disclosed that includes contacting a thin film composite membrane disclosed herein with a mixture containing one or more particles of different sizes; and separating the one or more particles via size-selective filtration.
[0048] In yet another aspect, a method of processing food is disclosed that includes contacting an impure food ingredient with a thin film composite membrane as disclosed herein; and separating contaminants from the impure food ingredient via size selective filtration.
[0049] In yet another aspect, a method of printing is disclosed that includes contacting a thin film composite film disclosed herein with one or more inks; and applying the one or more inks to a surface of an article. EXAMPLES
[0050] In order that the invention described herein may be more fully understood, the following examples are set forth. The examples described in this application are provided to illustrate the compounds, compositions, materials, devices, and methods provided herein, and should not be construed as limiting the scope thereof in any way.
[0051] material Materials: Sulfobetaine methacrylate (SBMA, 95%), 2-methacryloyloxyethyl phosphorylcholine (MPC, 97%), 2,2,2-trifluoroethyl methacrylate (TFEMA), 2,2-dimethoxy-2-phenylacetophenone (DMPA, 99%), N,N,N',N",N"-pentamethyldiethylenetriamine (PMDETA, 99%), 1,6-hexanedithiol (≥97%, FG), α-ethyl α-bromoisobutyrate (EBIB, 98%), CuBr2 (99%), sodium sulfate, Acid blue 45, Brilliant blue R, Chicago sky blue 6B, Direct red 80, Methyl orange, Ethyl orange and activated aluminum oxide (basic, Brockmann I, standard grade) were purchased from Sigma-Aldrich. Allyl methacrylate (or allyl methacrylate) (AMA, ≥98.0%), methanol (>99.8%), acetonitrile (≥99.5%), isopropyl alcohol (IPA, 99.5%), trifluoroethanol (TFE, ≥99.0%), sodium chloride (ACS certified), ethanol and riboflavin (98%) were purchased from Fisher scientific. Vitamin B12 was purchased from MP Biomedicals. d4-methanol (99.5%) and d6-DMSO (99.5%) were purchased from Cambridge Isotope Laboratories Inc. Ascorbic acid was purchased from GBiosciences. Commercially available nanofiltration membrane NP-30 (permeance: 1.75 LMH / b) was obtained from Sterlitech. Ultrafiltration support membrane UE-50 was obtained from Solecta membranes.
[0052] Example 1. Synthesis of poly(allyl methacrylate)-random-poly(sulfobetaine methacrylate) P(AM-r-SBMA) In this example, random copolymers with poly(allyl methacrylate) (AM) backbone and zwitterionic side groups used in the preparation of certain membranes of the present invention were synthesized as follows. First, 60 g of AM and 40 g of SBMA were mixed in the presence of 750 mL of 1:1 acetonitrile:methanol in a 2000 mL three-neck round-bottom flask. 1.55 mmol of α-ethyl bromoisobutyrate was then added to the mixture and stirred vigorously under a nitrogen environment. The ATRP reaction was initiated when a 1:1 acetonitrile:methanol solution (50 mL) containing CuBr2 (0.0614 mmol), ascorbic acid (0.619 mmol), and N,N,N',N",N"-pentamethyldiethylenetriamine (0.619 mmol) was cannulated into the pre-stirred solution of monomer and α-ethyl bromoisobutyrate. After the addition of the catalyst solution to the monomer mixture, the color of the reaction changed to light blue. The reaction was carried out at room temperature for 20 hours. After that, the reaction was stopped and the polymer solution was concentrated using a rotary evaporator. Finally, the remaining polymer mixture was precipitated into a 5:3 (v / v) mixture of hexane:ethanol. The resulting polymer was redissolved in 1:1 acetonitrile:methanol and further reprecipitated into a hexane:ethanol mixture for three consecutive times. Finally, the resulting polymer was dried under vacuum at ambient temperature for three days. The resulting copolymer was 1 It was characterized by H NMR (Figure 1D) and IR spectroscopy (Figure 1E).
[0053] Example 2. Formation of thin film composite membrane from P(AM-r-SBMA) In this example, the polymer described in Example 1 was used to fabricate the membrane. The P(AM-r-SBMA) copolymer was first dissolved in TFE (5 wt%) at room temperature and passed through both 1 μm and 0.45 μm filters consecutively. The resulting final polymer solution was degassed overnight in a sealed vial before coating the selective layer. A commercially available ultrafiltration support membrane (PS35 from Solecta) was then taped to the top of the glass plate. Finally, the selective layer was coated on top of the support membrane with the copolymer solution using a wire-wound metering rod (Gardco) (Gardco). Immediately after coating, the glass plate was rotated 180° and placed in a preheated oven (65° C.) for 12 minutes. The dry TFC membrane was then immediately immersed in DI water overnight.
[0054] Example 3. Synthesis of thiol-ene crosslinked thin film composite membrane In this example, the membrane of Example 2 with a selective layer of random copolymer PAM-r-SBMA was crosslinked as follows. Crosslinking of the pristine membrane (TCZ-0) was performed by UV-assisted thiol-ene click chemistry. The TCZ-0 membrane coated with P(AM-r-SBMA) copolymer was first immersed for 10 min in a solution of isopropanol (20 mL) containing 1 wt % each of 1,6-hexanedithiol and 2,2-dimethoxy-2-phenylacetophenone. The immersion was performed to saturate the hydrophobic domains with photoinitiator and thiol. Then, most of the solution (90%) was removed from the glass container and the membrane with the remaining solution was instantly UV cured (365 nm, 9 W / bulb, 4 bulbs) for different time scales ranging from 10 s to 40 s. After UV curing, the membrane was removed from the glass container and washed extensively with isopropanol and DI water. Finally, the washed membrane was kept in deionized water before any experiment.
[0055] The morphology of the membranes was determined by SEM imaging of freeze-fractured cross-sections of the membranes.
[0056] In Figures 2A-2C, SEM images of three different samples of membranes are shown. The coating layer can be observed for Figures 2B and 2C. Figure 2A represents the uncoated PS-35 support membrane, Figure 2B represents the uncrosslinked (TCZ-0) membrane with random zwitterionic support layer, and Figure 2C represents the crosslinked (TCZ-40) membrane. The TCZ-40 membrane was SEM photographed after keeping in TFE for 24 hours. The presence of the selective layer on the TCZ-40 membrane even after immersion in TFE solvent means that the membrane was successfully crosslinked. (Figures 2A-2C) 7000x magnification.
[0057] Example 4. Synthesis of poly(allyl methacrylate-random-poly(trifluoroethyl methacrylate)-random-poly(2-methacryloyloxyethyl phosphorylcholine) [P(AMA-r-TFEMA-r-MPC) terpolymer] First, allyl methacrylate (AMA) and trifluoroethyl methacrylate (TFEMA) monomers were purified through a basic alumina column and kept under nitrogen for further use. 11.81 g of 2-methacryloyloxyethyl phosphorylcholine (MPC) was dissolved in 260 mL of methanol in a 1000 mL three-neck round-bottom flask. Then, 11 g of AMA and 11.1 g of TFEMA were added and mixed thoroughly. The solution was continuously purged with nitrogen to remove dissolved oxygen from the mixture. Ethyl α-bromoisobutyrate (0.48 mmol) initiator was added to the reaction mixture and stirred vigorously under nitrogen environment. The catalyst solution was prepared in a separate vessel by dissolving CuBr2, ascorbic acid and N,N,N',N",N"-pentamethyldiethylenetriamine in methanol under nitrogen purge. The molar ratio between monomer:initiator:catalyst:ligand:reducing agent was chosen to be 402:1:0.0391:0.396:0.398. The reaction was initiated by transferring the catalyst solution to the pre-stirred solution of monomer and ethyl α-bromoisobutyrate using a cannula. The reaction mixture turned light blue after the addition of the catalyst solution to the monomer and initiator mixture. The reaction was carried out at room temperature for 20 hours, after which it was stopped by exposing the reaction mixture to air. The polymer solution was concentrated using a rotary evaporator. The polymer was then precipitated in a 3:2 (v / v) mixture of isopropanol:hexane. The resulting polymer was redissolved in methanol and reprecipitated in a mixture of isopropanol:hexane three times in succession. Finally, the resulting polymer was dried under vacuum at ambient temperature for three days. The resulting copolymer was then subjected to HPLC analysis. 1 It was characterized by 1 H NMR (Figure 3A) and IR (Figure 3B) spectroscopy.
[0058] Example 5. Formation of thin film composite membrane from P(AM-r-TFEMA-r-MPC) First, the P(AMA-r-TFEMA-r-MPC) terpolymer from Example 4 was dissolved in methanol at room temperature (4 wt%) and passed through a 1.2 μm Titan 3, HPLC filter, GMF membrane and 0.45 μm PTFE (ThermoScientific) successively. The resulting polymer solution was degassed overnight in a sealed vial before coating the selective layer. A commercial ultrafiltration support membrane (UE50 from Sterlitech) was taped onto a clean glass plate. The degassed polymer solution was then carefully coated onto the support membrane using a wire-wound metering rod (Gardco, #8, wet film thickness 20 μm). Once coating was complete, the glass plate was placed in a preheated oven (80° C.) for 4 min. The dry TFC membrane was then immediately immersed in DI water overnight.
[0059] Example 6. Synthesis of thiol-ene crosslinked thin film composite membrane UV-assisted thiol-ene click chemistry was used to perform crosslinking of the membrane described in Example 5. The membrane from Example 5, uniformly coated with P(AMA-r-TFEMA-r-MPC) terpolymer, was first immersed for 20 min in a solution (20 mL) of 1:1 isopropanol:hexane containing 2 wt% of 1,6-hexanedithiol and 2,2-dimethoxy-2-phenylacetophenone, respectively. The immersion was performed to saturate the hydrophobic domains with photoinitiator and thiol. Then, most of the solution (about 90%) was removed from the glass container, and the membrane with the remaining solution was instantly UV cured (365 nm, 9 W / bulb, and 4 bulbs) for different time scales ranging from 300 s to 14 min. After UV curing, the membrane was removed from the glass container and washed extensively with an isopropanol:hexane mixture followed by DI water. Finally, the washed membrane was kept in deionized water before any experiment.
[0060] Membrane characterization The films were characterized using attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). The morphology of the films was characterized using a Phenom G2 Pure Tabletop Scanning Electron Microscope (SEM) operated at 5 kV. Liquid nitrogen was used to freeze-fracture the samples for cross-sectional imaging. Prior to imaging, the samples were sputter-coated with gold-palladium.
[0061] Self-assembled nanostructures of copolymers Transmission electron microscopy (TEM) was used to characterize the morphology of the random copolymer self-assembled nanostructures. TEM images were obtained by FEI Technai Spirit in bright field mode operated at 80 keV. An 8% (w / v) copolymer solution was made in trifluoroethanol (TFE) solution. Films were cast from this solution by evaporation in Teflon dishes. A 2% copper(II) chloride (CuCl2) aqueous solution was used for 4 h for positive staining of zwitterionic domains. The reason for choosing CuCl2 was the formation of a stable complex between sulfobetaine and copper. The stained membranes were embedded in Embed 812 epoxy resin for 2 nights with frequent epoxy replacement, and 50 nm ultrathin sections cut using an ultramicrotome were placed on copper grids (200 mesh, Electron Microscopy Sciences). Nicki Watson from the Harvard CNS Center was responsible for the acquisition of the TEM images. Fast Fourier transform analysis was performed on the TEM images using ImageJ software.
[0062] Copolymer Molecular Weight Dynamic light scattering (DLS) was performed using a Brookhaven Instruments Nanobrook ZetaPALS instrument to estimate the approximate molecular weight of the synthesized copolymers. The light source was a 35 mW red diode laser with a nominal wavelength of 659 nm. The copolymers were first dissolved in TFE at a concentration of 1 mg / ml. DLS measurements were performed at a scattering angle of 90° and a temperature of 25°C, which was controlled by a thermostat. A 0.45 mm filter was used to remove dust before the light scattering experiments. Measurements were taken once the sample solutions were stabilized. Polyacrylonitrile standards in dimethylformamide (DMF) were used for calculation of the effective hydrodynamic radius and relative molecular weight by the instrument software (BIC Particle Solutions v.2.5).
[0063] XPS of different films To evaluate the surface elemental composition of the different films, X-ray photoelectron spectroscopy (XPS) was performed on a spectrometer using a monochromated A1Kα source. For survey spectra, scans were completed by averaging five scans at 1 eV steps with a pass energy of 200 eV from 10 eV to 1350 eV. For high-resolution spectra, data was collected by averaging ten scans at 0.1 eV steps with a pass energy of 50 eV for S2p, N 1s, O 1s, and C 1s photoelectron beams.
[0064] FTIR characterization of copolymers and films Fourier transform infrared (FTIR) spectra of the random zwitterionic copolymers and the corresponding membranes were measured using a 2 cm -1 and 400-4000cm -1 were recorded using attenuated total reflectance (ATR) technique with a FTIR spectrometer with a wide spectral range.
[0065] NMR analysis of copolymers The synthesized random zwitterionic copolymers were analyzed by an AV III 500 NMR spectrometer (500 MHz; Bruker, USA) using d-DMSO (with tetramethylsilane as an internal reference) as the solvent. 1 It was characterized by 1 H NMR spectroscopy.
[0066] Permeance measurements and single solute filtration The membrane filtration experiment was carried out using a 4.1 cm 2 The filtration was carried out using a 25 mm diameter membrane in a 10 ml Amicon 8010 stirred dead-end filtration cell (Millipore) with an effective filtration area of 1000 μm. The permeate mass was monitored using an electronic balance (Scout Pro) connected to a computer. A transmembrane pressure of 43.5 psi (3 bar) was utilized for all filtration experiments. During filtration, the Amicon cell was continuously stirred using a stir plate to minimize concentration polarization. Initially, deionized water was filtered through the membrane until the flux stabilized. The permeate mass was then recorded at 30 s intervals for the desired time and used to determine the transmembrane flux. Flux is defined as the flow rate through the membrane normalized by the membrane area. Permeance is a membrane property that normalizes the flux to account for the applied transmembrane pressure difference and is given by the following equation:
number
[0067] To determine the rejection of different dyes and salts, 10 mL of feed solution was used, then over 2 mL was filtered and finally the permeate was collected for further analysis. For the measurement of dye concentration, a UV-vis spectrometer (Genesys 10) was used. For the measurement of salt concentration, a conductivity meter (high range, VWR) was used. The relationship between salt concentration and conductivity was determined by first constructing a calibration curve using the stock feed solution. The rejection was calculated by the following formula:
number
[0068] Fouling experiment Fouling experiments were performed using the same apparatus as for permeance, but all membranes were permeated at 2.75 L / m to achieve similar hydrodynamic conditions at the membrane surface. 2 The transmembrane pressure was adjusted to have an initial water flux of .h.bar. Experiments were performed with three foulant solutions: (1) 1500mg / L oil-in-water emulsion (9:1 ratio soybean oil:DC193 surfactant), (2) 1g / L bovine serum albumin in PBS buffer (pH 7.4), and (3) 1g / L bovine serum albumin in 10mM CaCl2. In each fouling experiment, deionized (DI) water was first filtered through the membrane for 6 hours to obtain a pure water flux (J O ) was measured. The cell and reservoir were then filled with the contaminant solution. After filtering the contaminant solution for the desired time, the resulting flux (J) over time was calculated. The cell and reservoir were rinsed several times with DI water for cleaning and filled again with DI water to determine the reversibility of the fouling (final permeance).
[0069] Acid and Base Stability Tests First, the TCZ-20 membrane was carefully immersed in 0.5M NaOH for 24 hours. After that, the membrane was carefully washed with DI water so that the traces of base could be removed from the membrane surface. Finally, after base treatment, the pure water permeance and B12 rejection were tested and compared with the data before base treatment. It was observed that no significant changes were observed after base treatment, which provides a proper idea about the base stability of the prepared membrane. And for acid stability, the same protocol was followed with the only exception being that instead of using 0.5M NaOH, 0.5M HCl solution was used. Again, no significant changes are observed in the pure water permeance or B12 rejection after acid stability test.
[0070] Membrane Testing For membranes using P(AM-r-SBMA) copolymers: Membrane filtration experiments were performed using a 10 mL Amicon 8010 stirred dead-end filtration cell (Millipore) fitted with a 1 gal reservoir at 4.1 cm 2 The weight of the permeate was monitored by an electronic balance (Ohaus Scout Pro) connected to a computer. p ) is L p Rejection was determined by: = J / ΔP, where J is the volumetric flux of permeate and ΔP is the applied transmembrane pressure. For rejection measurements (both salt and dye), 10 mL of feed solution was loaded, filtered, approximately 2 mL of permeate was discarded, and then a further permeate fraction was collected for analysis. This was found to result in reliable and stable rejection values. Rejection (R) was determined by: R = (1-CP / CF)100%, where CF and CP are the feed and permeate concentrations, respectively. For fouling studies, we first determined the initial flux, fouled the membrane for 18-20 h, and finally gently rinsed the membrane with water before measuring the final flux.
[0071] For membranes with P(AMA-r-TFEMA-r-MPC) terpolymer: Membrane filtration experiments were performed using dead-end stirred cell filtration using the protocol described above. To estimate the rejection of both salts and dyes, the cell was filled with 10 mL of feed solution, the first ~1.5-2 mL of permeate was discarded, and subsequent fractions, previously shown to represent steady-state rejection, were collected for analysis (Bengani-Lutz, et at., High Flux Membranes with Ultrathin Zwitterionic Copolymer Selective Layers with ~1 nm Pores Using an Ionic Liquid Cosolvent. ACS Applied Polymer Materials 1, 1954-1959, (2019)). For fouling tests, deionized water was first filtered through the membrane until a constant permeance was reached. The foulant solution was then filtered for 18-20 h and the permeance was monitored. Finally, the cell and membrane were gently rinsed with deionized water and the final pure water flux was measured.
[0072] Example 7. Rejection of dyes by crosslinked P(AM-r-SBMA) membranes In this example, membranes prepared as described in Example 3 were used in experiments aimed at identifying their effective pore size or size cutoff. Dye molecules were used to investigate this property since they are rigid and their concentration is easily measured by UV-Vis spectroscopy. Retention experiments were performed with a cell volume of 10 mL and a 4.1 cm 2The experiments were carried out in an Amicon 8010 stirred dead-end filtration cell (Millipore) with an effective filtration area of 100 nm. Tests were performed at 43.5 psi. The cell was stirred to minimize concentration polarization effects, and pure water was passed through the membrane for at least 1 hour, after which the cell was emptied and a 100 mg / L solution of the probe dye in water was placed into the cell. After an equilibration period of at least 1 hour, samples were collected until sufficient for analysis by UV-visible spectrophotometry. The cell was rinsed several times with water. Pure water was filtered through the membrane until the permeate was completely clear before switching to a new probe dye. Figure 4 shows the retention of various negatively charged dyes by membranes made from the copolymer described in Example 1. Based on the filtration of these anionic dyes, the size cutoff of the membrane is estimated to be 1-1.2 nm. Furthermore, the rejection of these dyes is directly related to the molecular size of the dye, not its charge. Thus, such membranes can be used for size-selective separations. Figure 4 shows the rejection of anionic dyes of different molecular diameters. Table 1 shows the molecular size and charge of the dyes used in testing the effective pore size and their rejection by the membrane described in Example 3.
[0073] [Table 1]
[0074] Example 8. Rejection of dyes by crosslinked P(AM-r-TFEMA-r-MPC) membranes In this example, membranes prepared as described in Example 6 were used in experiments aimed at identifying their effective pore size or size cutoff. Dye molecules were used to investigate this property since they are rigid and their concentration is easily measured by UV-Vis spectroscopy. Retention experiments were performed with a cell volume of 10 mL and a 4.1 cm 2The experiments were carried out in an Amicon 8010 stirred dead-end filtration cell (Millipore) with an effective filtration area of 100 nm. Tests were performed at 43.5 psi. The cell was stirred to minimize concentration polarization effects, and pure water was passed through the membrane for at least 1 h, after which the cell was emptied and a 100 mg / L aqueous solution of the probe dye was placed in the cell. After an equilibration period of at least 1 h, samples were collected until sufficient for analysis by UV-visible spectrophotometry. The cell was rinsed several times with water. Pure water was filtered through the membrane until the permeate was completely clear before switching to a new probe dye. Figure 5 shows the retention of various negatively charged dyes by membranes made from the copolymer described in Example 4. Based on the filtration of these anionic dyes, the size cutoff of the membrane is estimated to be 1-1.2 nm. Furthermore, the rejection of these dyes is directly related to the molecular size of the dye, not its charge. Thus, such membranes can be used for size-selective separations. Figure 5 shows the rejection of anionic dyes of different molecular diameters.
[0075] Example 9. Separation of small molecules by crosslinked P(AM-r-SBMA) membranes In this example, the membranes prepared as described in Example 3 were used in the experiment to determine their small molecule separation ability. To estimate the small molecule separation ability of the membrane, a mixed solution of anionic dyes (Chicago Sky Blue 6B (0.88 nm) and methyl orange (0.79 nm)) at 0.05 mM each was filtered through the TCZ-40 membrane. Figure 6 shows the UV spectra for both dyes, the feed solution, and the permeate. It is clear from the figure that the spectrum of the permeate does not contain the Chicago Sky Blue 6B peak (597 nm), indicating that the dyes were fully retained and separated by the membrane. However, the methyl orange peak can still be observed, suggesting a suitable size-based separation efficiency of the membrane. Figure 6 shows the size-based small molecule separation ability of the TCZ-40 membrane monitored when two different dyes (each at 0.05 mM), Chicago Sky Blue 6B (0.88 nm) and methyl orange (0.79 nm), were mixed as the feed solution for the diafiltration experiment. The images show the UV spectra of the feed, permeate, and each single dye as a reference. Only methyl orange penetrated the TCZ-40 membrane, while Chicago Sky Blue 6B was fully retained.
[0076] Example 10. Separation of small molecules by crosslinked (AM-r-TFEMA-r-MPC) membranes In this example, the membranes prepared as described in Example 6 were used in the experiment to determine their small molecule separation capabilities. To estimate the membrane capacity for small molecule separation, a mixed solution of anionic dyes (Chicago Sky Blue 6B (0.88 nm) and methyl orange (0.79 nm)) at 0.05 mM each was filtered through the TCZ-40 membrane. Figure 6 shows the UV spectra for both dyes, the feed solution, and the permeate. It is clear from the figure that the spectrum of the permeate does not contain the peak of Chicago Sky Blue 6B (597 nm), indicating that the dyes were fully retained and separated by the membrane. However, the peak of methyl orange can still be observed, suggesting a suitable size-based separation efficiency of the membrane. Figure 7C shows that the size-based small molecule separation capabilities of the TERP-C-14 membrane were monitored when two different dyes (each at 0.05 mM), Chicago Sky Blue 6B (0.88 nm) and methyl orange (0.79 nm), were mixed as the feed solution for diafiltration experiments. The images show the UV spectra of the feed, permeate, and each single dye for reference. Only methyl orange permeated the TERP-C-14 membrane, while Chicago Sky Blue 6B was fully retained. Figure 7A shows the rejection of anionic dyes of various sizes by TERP-C-0 (uncrosslinked) and TERP-C-14 (crosslinked) membranes. Both membranes showed a sharp size cutoff. The crosslinked membrane showed a higher rejection than the uncrosslinked membrane, confirming that crosslinking results in a smaller effective pore size. Figure 7B shows the rejection performance of TERP-C-14 only.
[0077] Example 11. Salt Rejection by Crosslinked P(AM-r-SBMA) Membranes In this example, membranes prepared as described in Example 3 were used in experiments to determine their salt retention properties. The retention experiments were performed with a cell volume of 10 mL and 4.1 cm 2The experiments were carried out in an Amicon 8010 stirred dead-end filtration cell (Millipore) with an effective filtration area of 1000 s. The cell was stirred at 450 rpm and the tests were carried out at different pressures, e.g., 2, 3 and 4 bar, respectively. The cell was stirred to minimize concentration polarization effects. After passing pure water through the membrane for at least 1 h, the cell was emptied and 20 mM aqueous solutions of sodium chloride (NaCl), sodium sulfate (Na2SO4) and magnesium sulfate (MgSO4, Aldrich) were separately placed in the cell. After an equilibration period of at least 1 h, samples were collected for analysis by a standard conductivity probe. The cell was rinsed several times with water and pure water was passed through the membrane before switching to the other feed solutions. Figures 8A-8C show the rejection performance of 20 mM NaCl (Figure 8A), Na2SO4 (Figure 8B) and MgSO4 (Figure 8C) salts at various applied pressures for the uncrosslinked TCZ-0 and crosslinked TCZ membranes.
[0078] Example 12. Salt Rejection by Crosslinked P(AM-r-TFEMA-r-MPC) Membranes In this example, membranes prepared as described in Example 6 were used in experiments to determine their salt retention properties. The retention experiments were performed with a cell volume of 10 mL and 4.1 cm 2 The experiments were carried out in an Amicon 8010 stirred dead-end filtration cell (Millipore) with an effective filtration area of 1000 μm. The cell was stirred at 450 rpm and the tests were carried out at different pressures, e.g., 3 and 4 bar, respectively. The cell was stirred to minimize concentration polarization effects. After passing pure water through the membrane for at least 1 hour, the cell was emptied and 20 mM aqueous solutions of sodium chloride (NaCl) and sodium sulfate (Na2SO4) were separately placed in the cell. After an equilibration period of at least 1 hour, samples were collected for analysis by a standard conductivity probe. The cell was rinsed several times with water and pure water was passed through the membrane before switching to the other feed solution. Figures 9A and 9B show the rejection performance of 20 mM Na2SO4 (left) and NaCl (right) salts at various applied pressures for crosslinked TERP-CX (X=5, 10, 12, 14) membranes.
[0079] Example 13. Fouling test with crosslinked P(AM-r-SBMA) membrane using oil-water emulsion In this example, membranes prepared as described in Example 3 were used in experiments to determine their antifouling properties. Retention experiments were performed with a cell volume of 10 mL and 4.1 cm 2 The experiments were carried out in an Amicon 8010 stirred dead-end filtration cell (Millipore) with an effective filtration area of 2.75 Lm. -2 hr -1 Tests were performed with a flux of 0.01 µm. The pure water permeance of the membranes was measured for at least 6 hours, then the cell was emptied and a pollutant solution consisting of a 1500 mg / L oil-in-water (9:1) emulsion was filtered for 20 hours. Finally, the pure water permeance was measured again. Figures 10A-10C show the dead-end filtration of the pollutant solution through TCZ-30 (Figure 10A), TCZ-40 (Figure 10B), and the commercial membrane NP-30 (Figure 10C). The images show the initial water permeance (triangles and squares), followed by the permeance of the pollutant solution (circles). The membranes are then rinsed several times with water and the water permeance is measured again (triangles and squares). In the case of the TCZ-30 and TCZ-40 membranes, no flux loss was observed during and after exposure to the pollutant solution, while the commercial membrane shows a significant (about 48%) irreversible flux loss. The contaminant solution consisted of a 1500 mg / L oil-in-water (9:1) emulsion. J0 = 2.75 Lm -2 hr -1 .
[0080] Example 14. BSA / CaCl 2 Fouling test of crosslinked P(AM-r-SBMA) membrane using solution In this example, membranes prepared as described in Example 3 were used in experiments to determine their anti-fouling properties by filtering BSA protein. Retention experiments were performed with a cell volume of 10 mL and a 4.1 cm 2 The experiments were carried out in an Amicon 8010 stirred dead-end filtration cell (Millipore) with an effective filtration area of 2.75 Lm. -2 hr -1Tests were performed with a flux of 0.01%. First, the pure water permeance of the membrane was checked through the membrane for at least 5 hours, the cell was emptied, and a contaminant solution consisting of 1 g / L bovine serum albumin in 10 mM CaCl2 solution was placed in the cell. Protein filtration was performed for 18 hours, after which the pure water permeance was checked again. Prior to the pure water permeance, the cell was rinsed several times with water. Figures 11A-11B show the dead-end filtration of the contaminant solution through TCZ-40 (Figure 11A) and the commercial membrane NP-30 (Figure 11B). In the case of the TCZ-40 membrane, negligible flux loss was observed during and after exposure to the contaminant solution, while the commercial membrane shows a significant (about 27%) irreversible flux loss. The contaminant solution consisted of 1 g / L bovine serum albumin in 10 mM CaCl2 solution. J0 = 2.75 Lm -2 hr -1 .
[0081] Example 15. Fouling test with crosslinked P(AM-r-TFEMA-r-MPC) membrane using oil-water emulsion In this example, membranes prepared as described in Example 6 were used in experiments to determine their antifouling properties. Retention experiments were performed with a cell volume of 10 mL and 4.1 cm 2 The experiments were carried out in an Amicon 8010 stirred dead-end filtration cell (Millipore) with an effective filtration area of 2.75 Lm. -2 hr -1Tests were performed with a flux of 0.01 µm. The pure water permeance of the membranes was measured for at least 6 hours, then the cell was emptied and a pollutant solution consisting of a 1500 mg / L oil-in-water (9:1) emulsion was filtered for 18 hours. Finally, the pure water permeance was measured again. Figures 12A and 12B show the dead-end filtration of the pollutant solution through the commercial membranes NP-30 (Figure 12A) and TERP-C-14 (Figure 12B). The images show the initial water permeance (black), followed by the permeance of the pollutant solution (red). The membranes are then rinsed several times with water and the permeance is measured again (blue). In the case of the TERP-C-14 membrane, no flux loss was observed during and after exposure to the pollutant solution, while the commercial membranes show a significant (about 48%) irreversible flux loss. The pollutant solution consisted of a 1500 mg / L oil-in-water (9:1) emulsion. J0=2.75Lm -2 hr -1 .
[0082] Example 16. BSA / CaCl 2 Fouling test of crosslinked P(AM-r-TFEMA-r-MPC) membrane using solution In this example, membranes prepared as described in Example 6 were used in experiments to determine their anti-fouling properties by filtering BSA protein. Retention experiments were performed with a cell volume of 10 mL and a 4.1 cm 2 The experiments were carried out in an Amicon 8010 stirred dead-end filtration cell (Millipore) with an effective filtration area of 2.75 Lm. -2 hr -1Tests were performed with a flux of 0.01%. First, the pure water permeance of the membrane was checked through the membrane for at least 5 hours, the cell was emptied and a contaminant solution consisting of 1 g / L bovine serum albumin in 10 mM CaCl2 solution was placed in the cell. Protein filtration was performed for 20 hours, after which the pure water permeance was checked again. Prior to the pure water permeance, the cell was rinsed several times with water. Figures 13A and 13B show the dead-end filtration of the contaminant solution through the membrane TERP-C-14 (Figure 13B) together with the commercial membrane NP-30 (Figure 13A). In the case of the TERP-C-14 membrane, no flux loss was observed during and after exposure to the contaminant solution, whereas the commercial membrane shows a significant (about 27%) irreversible flux loss. The contaminant solution consisted of 1 g / L bovine serum albumin in 10 mM CaCl2 solution. J0 = 2.75 Lm -2 hr -1 .
[0083] Example 17. Non-aqueous cross-linking of P(AM-r-TFEMA-r-MPC) Cross-linking technique: The membrane was immersed in a solution of 2 wt% photoinitiator and cross-linker (see FIG. 16) in a 1:1 isopropanol:hexane mixture (20 mL) for 20 min, then the membrane was placed inside a glass container with its face covered by a glass plate. 30 seconds UV cured for 10 min. TIFF2024518727000005.tif38164
[0084] Example 18. Non-aqueous cross-linking of P(AM-r-TFEMA-r-MPC) Cross-linking technique: The membrane was immersed in a solution of 2 wt% photoinitiator and cross-linker (see FIG. 16) in a 1:1 isopropanol:hexane mixture (20 mL) for 20 min, then the membrane was placed inside a glass container with its face covered by a glass plate. 60 seconds UV cured for 10 min. TIFF2024518727000006.tif44164
[0085] Example 19. Non-aqueous cross-linking of P(AM-r-TFEMA-r-MPC) Cross-linking technique: The membrane was immersed in a solution of 2 wt% photoinitiator and cross-linker (see FIG. 16) in a 1:1 isopropanol:hexane mixture (20 mL) for 20 min, then the membrane was placed inside a glass container with its face covered by a glass plate. 90 seconds UV cured for 10 min. TIFF2024518727000007.tif44163
[0086] Example 20. Non-aqueous cross-linking of P(AM-r-TFEMA-r-MPC) Cross-linking technique: The membrane was immersed in a solution of 2 wt% photoinitiator and cross-linker (see FIG. 16) in a 1:1 isopropanol:hexane mixture (20 mL) for 20 min, then the membrane was placed inside a glass container with its face covered by a glass plate. 120 seconds UV cured for 10 min. TIFF2024518727000008.tif43163
[0087] Synthesis and crosslinking of membrane (P(AM-r-TFEMA-r-MPC)) The statistical / random copolymer represented here is a combination of three different monomers: 2-methacryloyloxyethyl phosphorylcholine (MPC), a zwitterionic monomer; trifluoroethyl methacrylate (TFEMA), a highly hydrophobic monomer; and allyl methacrylate (AM), a hydrophobic monomer with a C-C double bond that can readily undergo a thiol-ene click reaction (Figure 1B). The double bonds present in the AMA units can be crosslinked by a thiol-ene click reaction in the presence of dithiols (Figure 1B). This crosslinking reaction is carried out in a solvent that partitions preferentially into the hydrophobic domains but not into the zwitterionic domains. The solvent also plasticizes the TFEMA / AMA domains, increasing the mobility of the functional groups sufficiently to allow the crosslinking reaction. The crosslinked hydrophobic domains are more rigid, limiting the swelling of the zwitterionic domains when immersed in water. Thus, the effective pore size is smaller in the crosslinked ZAC-based membrane than in the uncrosslinked copolymer selective layer in water.
[0088] The P(AMA-r-TFEMA-r-MPC) terpolymer was successfully synthesized by the activator regenerated by electron transfer atom transfer radical polymerization (ARGET-ATRP) (Figure 1B). This controlled polymerization reaction almost exclusively polymerizes the highly reactive methacrylate groups, leaving the less reactive allyl side groups mostly intact. The presence of allyl double bonds (δ = 5.3 ppm; δ = 5.8 ppm) in the terpolymer was confirmed by the presence of the aryl groups of P(AMA-r-TFEMA-r-MPC). 1 The copolymer was confirmed by H NMR (FIG. 3A) and IR (FIG. 3B) analyses. The copolymer prepared is a white solid and is soluble in trifluoroethanol (TFE) and methanol.
[0089] P(AMA-r-TFEMA-r-MPC) was coated onto a commercial support membrane (Sterlitech, UE50) to form a TFC membrane. To achieve this, P(AMA-r-TFEMA-r-MPC) was dissolved in methanol to form a 4 wt% solution, which was then coated on top of the support membrane by using a wire-wound metering rod. This coated membrane was placed in an oven preheated to 80°C for 4 minutes. Finally, the membrane was removed from the oven and immersed in distilled water overnight. This thin film composite (TFC) membrane, when produced without any crosslinking, is called TERP-C-0. Random copolymers of TFEMA and MPC microphases segregate to form disordered bicontinuous domains of about 1.3 nm (Bengani-Lutz, et al., Self-Assembling Zwitterionic Copolymers as Membrane Selective Layers with Excellent Fouling Resistance: Effect of Zwitterion Chemistry. ACS Applied Materials & Interfaces 9, 20859-20872, (2017)). Copolymers of AMA and the similar zwitterionic monomer sulfobetaine methacrylate (SBMA) also formed very similar morphologies (Lounder, et al., Zwitterionic Ion-Selective Membranes with Tunable Subnanometer Pores and Excellent Fouling Resistance. Chemistry of Materials 33, 4408-4416, (2021)). Thus, upon casting, P(AMA-r-TFEMA-r-MPC) was expected to self-assemble into a similar morphology, resulting in a network of MPC-rich nanodomains that are small enough to fit into these “nanochannels” and allow the permeation of water and solutes, held together by the hydrophobic TFEMA / AMA-rich domains ( Figure 1 A).After formation of these TFC films, the hydrophobic AM repeat units were crosslinked using a thiol-ene click reaction with dithiols (Figure 1B). Uncrosslinked TERP-C-0 films were immersed for 20 min in a solution of an isopropanol:hexane mixture containing 2 wt% each of 2,2-dimethoxy-2-phenylacetophenone (DMPA, photoinitiator) and 1,6-hexanedithiol. The films were then exposed to UV light for various times ranging from 300 s to 14 min. The films are labeled TERP-C-5, TERP-C-10, TERP-C-12, and TERP-C-14, respectively, with the last two digits designating the UV cure time (Table 2). During UV cure, DMPA, a photoinitiator, generated radicals from 1,6-hexanedithiol, which then reacted with the allylic double bonds of the AM repeat units. This resulted in cross-linking of hydrophobic domains, increasing rigidity and preventing swelling of the zwitterionic nanochannels in aqueous environments to an extent related to the extent of the reaction.
[0090] [Table 2]
[0091] The morphology of the crosslinked and uncrosslinked TFC membranes was examined by scanning electron microscope (SEM) imaging (Figures 14A-14C). In both TERP-C-0 and TERP-C-14 membranes, a thin selective layer is clearly visible on top of the support membrane. The thickness of this layer can potentially be further reduced by improving the coating process, resulting in up to 50 times higher membrane permeance. Importantly, Figure 2C was obtained after immersion of the TERP-C-14 membrane in TFE, a solvent that readily dissolves the uncrosslinked P(AMA-r-TFEMA-r-MPC). The fact that the selective layer is visually unchanged indicates that crosslinking improves the solvent stability of this layer. This opens the door for future potential uses of crosslinked ZAC membranes in further applications, including solvent-resistant nanofiltration and organic solvent nanofiltration (OSN).
[0092] Membrane permeance and selectivity The performance of the newly fabricated membranes was characterized using dead-end stirred cell filtration (Table 3). The uncrosslinked TERP-C-0 membrane, like the previous ZAC-based membranes, had a filtration rate of 6.66 ± 0.45 L / m 2 The membranes showed a pure water permeance of 1.5 h.bar. The pure water permeance of the membranes decreased with increasing crosslinking time, accompanied by a sharp increase in the rejection of various solutes (Table 3). A gradual increase in UV curing time from 300 s to 14 min results in a decrease of about 93% in the pure water permeance compared to the uncrosslinked membrane (Figure 15). This phenomenon means that most of the available AMA groups were successfully crosslinked in that given time frame. These reaction times are significantly shorter than other crosslinking chemistries such as photopolymerization of these allyl groups.
[0093] Membrane selectivity is considered one of the most important parameters for determining the final performance and applications in related fields. The effect of UV irradiation on the selectivity of crosslinked membranes was first screened by tracking the rejection of two neutral small molecule solutes, vitamin B12 (VB12; Stokes diameter 1.48 nm) and riboflavin (Stokes diameter approximately 1 nm). The uncrosslinked TERP-C-0 membrane showed rejection of vitamin B12 and riboflavin of 87.5% and 18%, respectively, which was consistent with previous studies. Increasing the UV exposure time resulted in an increase in the rejection of both solutes, which stabilized after 12–14 min, consistent with the permeance data (Table 3).
[0094] P(AMA-r-TFEMA-r-MPC) does not possess any functional groups and is essentially electrostatically neutral. As a result, its selectivity was expected to be largely unaffected by the charge of the solute and to exhibit mostly size-based selectivity. To validate the size-selective nature of the TERP-C-0 and TERP-C-14 membranes, the rejection rates of different dyes with various numbers of negative charges were investigated (Table 3; Figure 7A). This set of dyes has been used previously and shown to be a good predictor of ZAC-based membrane selectivity. In this particular study, calculated diameters estimated from molecular volumes were used because the Stokes radii of many of these dyes are not consistently reported in the literature. These calculated diameters were estimated by calculating the molecular volume of each molecule (Molecular Modeling Pro) and then calculating the diameter of a sphere of the same volume. Thus, it is a significant underestimate that does not take into account the geometry or hydration, but it is reliable and has been established to predict the rejection curves of solutes by ZAC-based membranes. Both the uncrosslinked membranes TERP-C-0 and the highly crosslinked (hypercrosslinked) TERP-C-14 showed consistent rejection, with the rejection of each dye being linked to its size independent of the number of anionic charges (Figure 7A). This means that charge does not significantly affect selectivity. Rejection of all dyes by TERP-C-14 was higher compared to that of uncrosslinked TERP-C-0, further confirming the reduction in effective pore size upon crosslinking.
[0095] [Table 3]
[0096] To demonstrate the ability of the TERP-C-14 membrane for the separation of small molecule mixtures, an equimolar mixture (0.05 mM) of two dyes, methyl orange (0.79 nm) and Chicago Sky Blue 6B (0.88 nm), was filtered. No trace of Chicago Sky Blue 6B was found in the permeate, as evidenced by the absence of a characteristic UV-visible spectral peak at 597 nm (Figure 7C), suggesting that the membrane is able to fully retain the dye. Methyl orange was still able to permeate the membrane, demonstrating fractionation of this solution mixture.
[0097] Due to the very small effective pore size of the highly crosslinked TERP-C-14 membranes, we decided to test the ion separation capabilities of these crosslinked r-ZAC membranes, which show excellent anion selectivity due to a combination of steric effects and ion-zwitterionic interactions. We measured the rejection of sodium monovalent and divalent anion salts, specifically NaCl and Na2SO4, using 20 mM solutions at transmembrane pressures of 3 and 4 bar (Figures 9A and 9B). The uncrosslinked TERP-C-0 membranes were similar to previous reports on other uncrosslinked ZACs. 37 Consistent with this, the membranes showed very low salt rejection (<10%). With only 5 min of UV exposure, the salt rejection increased significantly, to about 95% for Na2SO4 and about 20% for NaCl. Longer UV curing resulted in a gradual but slow increase in rejection for both salts. Crosslinking for 14 min increased the rejection of Na2SO4 to 98% and NaCl to 32%. Even shorter UV exposures can result in membranes with high salt selectivity, allowing for rapid and scalable fabrication.
[0098] Fouling resistance Fouling is one of the biggest obstacles to the long-term use of membranes in many critical applications. Fouling is broadly defined by the accumulation and adsorption of various feed components on the membrane surface, resulting in performance loss. Managing fouling through periodic cleaning and membrane replacement is one of the largest contributors to the cost of membrane operation. For this reason, fouling resistance is highly desired for new membrane materials. Membranes with various ZAC selective layers exhibit excellent resistance to fouling and completely resist irreversible fouling even with very challenging feed solutions. As a result, the resistance of these thiol-ene crosslinked ZAC membranes to fouling by various pollutant solutions was validated. A state-of-the-art commercial nanofiltration membrane (NP-30) was also used as a benchmark.
[0099] Dead-end filtration experiments were performed to characterize the fouling resistance. In each experiment, first, the initial pure water permeance was measured by filtering deionized water until the flux stabilized. A representative foulant solution is then filtered for 20 hours. The membrane and filtration cell were then washed several times with deionized water. Finally, the deionized water was filtered again to determine the reversibility of the permeance decrease with physical cleaning methods alone. The pure water permeance was measured again to verify the reversibility of the fouling. The disclosed crosslinked membrane showed a high degree of removal of oil droplets. The feed solution was observed to be translucent and grayish in color due to light scattering by the oil droplets.
[0100] The first type of contaminant studied was an oil-in-water emulsion. The oil and gas industry generates large volumes of oily wastewater, which is constantly generated in the form of refinery wastewater, frac water, and produced water. To simulate these types of flows, a 1.5 h / L oil-in-water emulsion prepared using a 9:1 ratio of soybean oil to DC193 surfactant was used. Both the commercial NF membrane and TERP-C-14 effectively removed the oil and produced a clear permeate as expected. The commercial nanofiltration (NP-30) membrane (Figure 12A) showed significant fouling, losing nearly 48% of its initial flux during contaminant filtration. This irreversible flux loss was not recoverable by simple physical cleaning processes. This data is typical of the state-of-the-art membranes on the market today. In contrast, the TERP-C-14 crosslinked membrane did not show any significant flux loss even during the filtration of oil emulsions. After filtration of the polluted solution, with a simple water rinse, the pure water flux appeared similar to its initial value. This trend is surprising and indicates the excellent anti-fouling properties of the crosslinked membrane, whereas most reported membranes tend to show at least some flux loss during the filtration process.
[0101] A second series of fouling experiments was performed with bovine serum albumin (BSA), a well-known protein that is often used to characterize the fouling tendency of membranes due to its strong tendency to readily adsorb onto surfaces. The degree of fouling by BSA and other proteins is greatly influenced by the solution composition, including ionic strength, pH, and other solution properties. For this experiment, a 1 g / L solution of BSA in 10 mM CaCl2 (pH: 6.4) was used. Calcium ions can lead to gel formation through complexation with various anionic groups common to membrane materials, enhancing the fouling tendency of the solution. This solution is therefore expected to constitute a particularly challenging contaminant for membranes.
[0102] Figures 13A and 13B show the dead-end filtration of 1 g / L BSA (bovine serum albumin) protein in 10 mM CaCl2 solution by NP-30 (Figure 13A) and TERP-C-14 (Figure 13B). Similar to the oily water experiment, the commercial nanofiltration NP-30 membrane lost approximately 27% of its initial flux during filtration of the contaminant. This irreversible flux loss was not recovered after rinsing with pure water. In contrast, no flux reduction was observed during filtration of this BSA solution through the TERP-C-14 membrane. The water flux before and after this fouling run was the same. This further demonstrates the improved fouling resistance of these zwitterionic membranes.
[0103] Preparation and crosslinking of membrane (P(AM-r-SBMA)) The crosslinked ZAC in this study was a statistical / random copolymer of sulfobetaine methacrylate (SBMA), a zwitterionic monomer, and allyl methacrylate (AM), a hydrophobic monomer featuring a C=C double bond in its side group capable of undergoing a thiol-ene reaction. The AM units are crosslinked by a thiol-ene reaction with a dithiol (Figure 1C, Figure 1F). This crosslinking reaction prevents swelling of the zwitterionic domains when immersed in water, especially when carried out in a solvent / plasticizer that preferentially partitions into the hydrophobic domains. As a result, the effective pore size of the crosslinked ZAC-based membrane in water is smaller than that of its uncrosslinked counterpart. The time scale required to crosslink the hydrophobic phase was too long to be implemented in roll-to-roll manufacturing.
[0104] Atom transfer radical polymerization with electron transfer regeneration of activators (ARGET-ATRP) was used to synthesize P(AM-r-SBMA) (Figure 1C). The lower reactivity of the allyl group in this controlled polymerization reaction scheme allowed AM to be polymerized exclusively through its more reactive methacrylate group while keeping the allyl side groups intact. This synthetic scheme is highly scalable because ARGET-ATRP is a robust polymerization technique that allows the synthesis of designed polymers and copolymers at low temperatures without the need to remove water and protic species. 1 H NMR confirmed the active presence of allylic double bonds (δ = 5.3 ppm; δ = 5.8 ppm) in the structure of P(AM-r-SBMA) (Figure 1D). The total SBMA content of the copolymer was calculated to be 47 wt% from this spectrum. This is in close agreement with our content of SBMA in the reaction mixture. Given the relatively low conversion of 10%, the close agreement between the composition of the copolymer and the reaction mixture implies a near-random arrangement of AM and SBMA repeat units along the polymer backbone. This low conversion was used in the presented data set to ensure that the solution would not form a crosslinked gel, but in subsequent experiments with similar crosslinkable copolymers containing AM and zwitterionic monomers, conversions of over 50% have been achieved without gelation. This indicates that this technique may be used in the future for reliable and scalable synthesis of this copolymer without environmental impacts significantly exceeding those of most specialty polymer products. The copolymer prepared is a white solid that is soluble in trifluoroethanol (TFE) and dimethylsulfoxide (DMSO).
[0105] The low solubility of P(AM-r-SBMA) in common solvents limited the use of gel permeation chromatography (GPC) to measure its molar mass. To estimate the relative molecular weight of the copolymer, dynamic light scattering (DLS) was performed on dilute solutions of the copolymer in TFE. The copolymer had a molecular weight of 2.6x10 based on a polyacrylonitrile standard in dimethylformamide. 6It showed an effective hydrodynamic radius of 60.8 ± 1 nm, corresponding to a molar mass in g / mol. It is important to state that the molecular weights expressed here are relative values of polymer segments with comparable hydrodynamic radii. Although polymer chain aggregation and polymer-solvent interactions greatly affect the relationship between absolute molar mass and hydrodynamic radius, the relative molar mass calculated by GPC is subject to similar limitations. This relatively high relative molar mass therefore confirms that the synthesized copolymer is a long-chain polymer.
[0106] The morphology of the self-assembled nanostructures of the synthesized ZAC, P(AM-r-SBMA), was characterized using TEM. The sulfobetaine groups and copper(II) ions form a stable complex, which was positively stained by immersion in 2% aqueous CuCl2 for 4 h to stain the zwitterionic nanodomains. As seen in the bright-field TEM image in Figure 17, P(AM-r-SBMA) self-assembles to form an interconnected, bicontinuous network of hydrophobic (light) and zwitterionic (dark) nanodomains. The dark zwitterionic domains are interconnected, indicating a percolation network through the film that allows water transmission. Fast Fourier transform (FFT) analysis (Figure 17, inset) shows an average domain size of 1.4 nm. This morphology is similar to that observed for other ZACs.
[0107] P(AM-r-SBMA) was coated onto a commercially available support membrane (Solecta, PS-35) to form a TFC membrane. For this purpose, P(AM-r-SBMA) was dissolved in TFE to form a 5 wt% solution, which was coated on top of the support using a wire-wound metering rod. This coated membrane was placed in an oven preheated to 65 °C for 12 min. Finally, the membrane was removed from the oven and immediately immersed in DI water overnight. This TFC membrane was fabricated without crosslinking and is called TCZ-0. Upon casting, the self-assembly of ZAC formed a network of zwitterionic nanodomains, which allows the permeation of water and solutes small enough to enter the zwitterionic nanochannels, held together by the hydrophobic AM-rich domains (Figure 17).
[0108] After formation of these TFC membranes, the hydrophobic AM repeat units were crosslinked using a thiol-ene click reaction with a dithiol (Figure 1C). Uncrosslinked TCZ-0 membranes were immersed in a solution of IPA containing 1 wt% each of DMPA (photoinitiator) and 1,6-hexanedithiol for 10 min. The membranes were then exposed to UV light for various times ranging from 10 to 40 s. The membranes are identified as TCZ-10, TCZ-20, TCZ-30, and TCZ-40, respectively, with the last two digits designating the UV cure time in seconds. During UV cure, DMPA acted as a photoinitiator, generating radicals on the 1,6-hexanedithiol, which then reacted with the allylic double bonds of the AM repeat units (Figure 1F). This resulted in crosslinking of the hydrophobic domains, increasing rigidity and preventing swelling of the zwitterionic nanochannels in an aqueous environment, which was determined by the extent of the reaction.
[0109] The crosslinking of the selective layer was confirmed by analyzing the chemical composition of the selective layer using ATR-FTIR spectroscopy (Figure 18). -1Most of the peaks corresponding to the SBMA groups and backbone remained similar in the TCZ-0 and TCZ-40 films as expected, including a sharp peak at 985–1004 cm. The main difference between the spectra was the peaks involved in –CH=C blending (985–1004 cm). -1 The lower peak intensity of the TCZ-40 film compared to TCZ-0 can be attributed to the consumption of allylic double bonds by thiol-ene crosslinking during UV curing.
[0110] The surface elemental composition of these two films was further characterized using XPS (Figures 19A-19B). The characteristic peaks of O1s, N1s, C1s, and S2p are present in the survey spectrum of both films (Figure 19A), which is in good agreement with the elemental composition of the selective layer. The high-resolution spectrum for the S2p region (Figure 19B) allowed for a deeper characterization of the bonding structure around the sulfur groups. The TCZ-0 film has a high concentration of SO3 on the SBMA repeat unit. - The spectrum of the crosslinked TCZ-40 membrane showed only one S2p peak (168.2 eV) arising from the thioether group. The spectrum of the crosslinked TCZ-40 membrane showed two distinct S2p peaks, one at 163.5 eV and the other at 168.2 eV. The additional peak was associated with the thioether group (RSR) formed in the thiol-ene click reaction. These results further support the expected crosslinking reaction.
[0111] The morphology of the coated membranes was investigated by SEM imaging (Figures 2A-2C). A thin selective layer on top of the supported membrane can be clearly seen in both TCZ-0 and TCZ-40 membranes. This layer adheres to the support by the polymer partially penetrating into the pores of the support to form physical anchors, as well as by intermolecular interactions. Since polysulfone is known to generate free radicals upon UV irradiation that can react with allyl groups in the copolymer, it is also possible that there is some chemical bonding between the support and the layer upon crosslinking. The thickness of this layer could potentially be further reduced by improving the coating process, resulting in up to 50 times higher membrane permeance, as demonstrated with other ZAC membrane chemistries.
[0112] The membrane was immersed in TFE, a solvent that readily dissolves uncrosslinked P(AM-r-SBMA). The fact that the selective layer is visually unchanged indicates that crosslinking improves the solvent stability of this layer. This opens the door for future potential use of crosslinked ZAC membranes in additional applications, including solvent-resistant nanofiltration and organic solvent nanofiltration (OSN).
[0113] Membrane permeability and selectivity Dead-end stirred cell filtration experiments were used to characterize the membrane performance (Table 4). [Table 4]
[0114] The average permeance of the uncrosslinked TCZ-0 membrane is 5.5±0.9Lm -2 h.bar. Crosslinking of the hydrophobic domains of P(AM-r-SBMA) results in a decrease in the effective pore size, as demonstrated by the decrease in water permeance with increasing solute rejection. Increasing the UV cure time from 10 to 40 seconds results in a decrease in permeance of approximately 80% compared to the uncrosslinked system (Figure 20), with the change plateauing after only about 30-40 seconds of exposure time. This trend implies near complete crosslinking of the available AM groups in less than one minute, an order of magnitude less than would be required when using other crosslinking chemistries such as photopolymerization of these allyl groups.
[0115] One of the most important parameters of a membrane is its selectivity. As an initial screen to characterize how UV exposure time affects the selectivity of these membranes, two neutral small molecule solutes, vitamin B12 (VB12; Stokes diameter 1.48 nm) and riboflavin (Stokes diameter approximately 1 nm), were used as probes. The rejection rates of vitamin B12 and riboflavin by the TCZ-0 membrane were 82% and 33%, respectively, which was consistent with previous studies. The rejection rates of both solutes increased with increasing exposure time and stabilized again after 30–40 s, consistent with the permeance results (Table 4).
[0116] The selectivity of uncrosslinked ZAC membranes is governed by solute size. Since the synthesized zwitterionic copolymers are electrostatically neutral, the selectivity of the membranes is not significantly affected by solute charge, and charged and neutral solutes of roughly similar geometries share rejection curves along with low salt rejection. To characterize the size-based selectivity of TCZ-0 and TCZ-40 membranes, the rejection of various negatively charged dyes was measured (Table 1). Note that the calculated diameter used here is not the Stokes diameter, but an estimate of molecular size calculated from molecular volume, obtained using Molecular Modelling Pro software. Although this measure is an underestimate of the actual Stokes diameter as it does not consider hydration or molecular geometry effects, it has been proven to be reliable and predictive of the rejection properties of solutes by ZAC-based membranes.
[0117] Figure 4 shows the rejection of different anionic dyes by TCZ-0 and TCZ-40 membranes. The rejection of different anionic dyes with different charges fit a single rejection curve for both membranes TCZ-0 and TCZ-40 (Figure 4), implying limited charge effects, as discussed earlier. The TCZ-40 membrane rejected all dyes to a higher extent than the TCZ-0 membrane, further supporting the reduction in effective pore size. The final rejections of these dyes were all above 85%, implying very small pores that could potentially exhibit salt rejection based on steric effects and zwitterion-ion interactions.
[0118] To demonstrate the ability of the TCZ-40 membrane to separate dye mixtures, we filtered a solution containing a mixture of two dyes, Chicago Sky Blue 6B (0.88 nm) and methyl orange (0.79 nm), at the same concentration (0.05 mM). The resulting permeate was free of Chicago Sky Blue 6B, as documented by the UV-visible spectrum lacking the characteristic peak of this dye at 597 nm (Figure 6). Methyl orange still permeated the membrane, indicating fractionation of this mixture.
[0119] The stability of these membranes in strong acids and strong bases often used for chemical cleaning was tested. The permeance and vitamin B12 rejection of one of the thiol-ene crosslinked ZAC membranes, TCZ-20, showed no measurable change after 24 hours of immersion in either 0.5 M NaOH or 0.5 M HCl (Figure 22). This confirms the chemical stability of these selective layers. These membranes feature selective layers fabricated from crosslinkable ZAC poly(aryl methacrylate-random-sulfobetaine methacrylate) (P(AM-r-SBMA)), the chemical structure of which is shown in Figure 1C. We observe changes at UV exposure times >5 min; further increases in exposure time result in smaller pore sizes. A key feature of this work is the utilization of a new crosslinking chemistry, thiol-ene click chemistry with dithiols, to reduce UV exposure times to a few seconds. We show that crosslinking for as little as 10 seconds results in significant changes in pore size, and variation in exposure time between 10 and 40 seconds further tunes the effective pore size, salt rejection, and monovalent / divalent ion selectivity. The resulting membranes have high Cl-ion selectivity compared to many state-of-the-art membranes. - / SO4 2- Selectivity was demonstrated (Table 5).
[0120] [Table 5]
[0121] As mentioned herein, the rejection of even the smallest probe dyes by TCZ-40 is very high. This means extremely small pores that may show selectivity. As discussed in recent studies, membranes with highly crosslinked ZAC selective layers show anion selectivity related to steric effects as well as zwitterion-ion interactions. Therefore, it is reasonable to expect selectivity between salt ions in the thiol-ene crosslinked membranes discussed herein. To test this hypothesis, we measured the rejection of various salts, specifically NaCl, MgSO4, and Na2SO4, using 20 mM solutions at transmembrane pressures of 2-4 bar (Figures 8A-8C). The uncrosslinked TCZ-0 membrane showed very low salt rejection (<20% for all salts) and separation factors very close to 1 (Table 6), consistent with previous uncrosslinked ZAC membranes. UV curing resulted in an increase in the rejection of all four salts, but the pattern in these changes depended on the nature of each salt. After only 10 seconds of UV exposure, we observed a significant increase in salt rejection upon crosslinking. Such rapid tuning of selectivity is unique to this system and is made possible by the high reaction rate of thiol-ene chemistry as well as the unique separation mechanism in ZAC-based membranes.
[0122] [Table 6]
[0123] All membranes were tested at room temperature. The separation factors were - Ion passage rate and SO4 2- It is defined as the ratio of the ion transmission rate to the ion transmission rate and is calculated by the following formula:
number
[0124] The most significant change over the shortest time was for Na2SO4, whose rejection at 2 bar rose from about 4% to about 70% after only 10 seconds of exposure. The rejection of Na2SO4 did not increase significantly with further crosslinking, with a rejection of 78% after 40 seconds. Interestingly, the rejection of Na2SO4 was consistently higher than that of MgSO4, but this difference was more pronounced for the shortest exposure times of 10 and 20 seconds. The rejection of MgSO4 also rose more slowly, similar to the trends in permeance and organic solute rejection, becoming relatively stable after 30-40 seconds. Size-based selectivity contributes to these trends, but the fact that crosslinked ZAC membranes can, under some circumstances, exhibit selectivity between ions of similar charge and size implies that zwitterion-ion interactions also play an important role. In other words, both the size of the ions and their affinity for SBMA affect selectivity. In this case, the difference in trends may result from differences in cation partitioning into the zwitterionic nanochannels, which also affect sulfate permeability due to electroneutrality. At higher crosslinking degrees, the rejection of magnesium increases due to size exclusion.
[0125] The rejection of NaCl increased much less with crosslinking time than those of Na2SO4 and MgSO4, reaching a maximum of 29% after 40 s of crosslinking. As a result, the NaCl / Na2SO4 separation factor increased with increasing irradiation time (Table 6). The largest jump was observed within 10 s, and the separation factor nearly plateaued by 40 s. As a result, these thiol-ene crosslinked membranes have highly tunable monovalent / divalent ion selectivity along with fast and easy fabrication. For example, membranes crosslinked for shorter times (e.g., TCZ-10) can remove divalent anions with limited cation separation, whereas highly crosslinked membranes (e.g., TCZ-40) can be used to selectively remove all divalent ions with relatively low NaCl rejection.
[0126] Fouling resistance Fouling, associated with the adsorption and accumulation of feed components on the membrane surface, is one of the most important barriers preventing the more widespread use of membranes in many applications. Novel membranes must therefore resist fouling by preventing the adsorption of organic pollutants on their surface. ZAC membranes have been shown to exhibit unparalleled resistance to fouling due to the presence of highly hydrated zwitterionic groups covering their surface.
[0127] We tested the resistance of these thiol-ene crosslinked ZAC membranes to fouling by a variety of pollutants. A commercially available state-of-the-art nanofiltration membrane (NP-30) was also used as a benchmark to compare fouling data with our crosslinked membranes.
[0128] We performed static fouling experiments involving immersion of the thiol-ene crosslinked ZAC membrane TCZ-40 in a solution of the protein bovine serum albumin (BSA) in phosphate buffered saline (PBS). BSA is frequently used to test the fouling tendency of membranes as it tends to readily adsorb to surfaces. After 24 hours in this solution, the membrane was removed and rinsed with DI water. The proteins adsorbed to the membrane were then stained using Gelcode Blue Safe Protein Stain. The deep blue color of the fouled NP30 membrane indicated significant protein adsorption, whereas little, if any, blue staining was observed in the TCZ-40 membrane (Figure 23). This indicated that the crosslinked ZAC membrane TCZ-40 exhibited minimal, if any, protein fouling, outperforming commercial membranes in terms of fouling resistance, even in this simplified system.
[0129] Although static fouling experiments are promising, membrane fouling during operation is much more complex. Fouling can occur with a wide range of chemical species depending on the feed, and concentration polarization and hydrodynamics during filtration further enhance the fouling tendency. Therefore, the majority of our fouling analysis utilized dead-end stirred cell filtration experiments, which are often considered the worst-case scenario for fouling due to the gradual accumulation of contaminants in the filtration cell. We also screened for multiple contaminants.
[0130] The first contaminant selected was an oil-in-water emulsion. Large volumes of oily wastewater are regularly generated by the oil and gas industry in the form of produced water, frac water, and refinery wastewater. Proper disposal of these wastewater streams remains a significant challenge. Therefore, we challenged two of our crosslinked membranes (TCZ-30 and TCZ-40) with a 1.5 g / L oil-in-water emulsion with a 9:1 ratio of soybean oil to DC193 surfactant, selected to represent such an oily wastewater stream.
[0131] Figures 10A-10C show data from oil-in-water emulsion fouling experiments carried out in dead-end stirred cell filtration mode for TCZ-30 (Figure 10A), TCZ-40 (Figure 10B), and the commercial nanofiltration membrane NP-30 (Figure 10C). In each case, deionized water was filtered to determine the initial pure water permeance, after which the foulant solution was filtered for 20 h. The filtration cell and membrane were then rinsed several times with water to simulate physical cleaning by forward flushing with clean water. The pure water permeance was then measured again to examine the reversibility of the fouling. All three membranes showed high removal of oil droplets, as indicated by the appearance of the feed and permeate. The feed was translucent and grayish due to light scattering by the droplets, while the permeate was clear. Figure 10A (inset) shows this for the TCZ-30 membrane. Permeates from the other three membranes were similar.
[0132] During the fouling experiments, both TCZ-30 and TCZ-40 membranes did not show a significant decrease in flux even during the filtration of contaminants. After water rinsing, the pure water flux remains the same as the initial value. This performance is exceptional, since most membranes show at least some flux decrease during the filtration step. The data obtained from the commercial NP-30 membrane (Figure 10C) are representative of the state of the art. This membrane fouled significantly and lost nearly 48% of its initial flux during the filtration of contaminants. This loss was not reversible by physical cleaning processes.
[0133] We also performed fouling experiments with two feed solutions containing BSA. The fouling potential of BSA and other proteins is highly dependent on solution properties including ionic strength and pH. Therefore, we prepared 1 g / L solutions of BSA in two different matrices. The first solution contained BSA dissolved in PBS (phosphate buffered saline), which is a very common system for initial fouling screening in the literature. As an additional challenge, we prepared a 1 g / L solution of BSA in 10 mM CaCl2 (pH: 6.4). Calcium ions have a tendency to form gels by complexation with multiple anions, resulting in a high fouling tendency of the solution.
[0134] Figures 21A-21B show the dead-end filtration of 1 g / L BSA protein in PBS by TCZ-30 (Figure 21A) and TCZ-40 (Figure 21B). The contaminant solution was filtered through both membranes for 18 h. No flux reduction was observed during contaminant filtration for either membrane. After gentle water rinsing, no irreversible flux loss was measured. This phenomenon clearly indicates the exceptional fouling resistance of these ZAC membranes.
[0135] Additionally, we also studied the fouling of these membranes using the more challenging protein solution mentioned above, 1 g / L BSA in 10 mM CaCl2 solution for 20 hours (Figures 11A-11B). The TCZ-40 membrane showed a negligible flux decrease during filtration of contaminants over 20 hours, which was fully recovered after a simple water wash. In contrast, the commercial NP-30 showed a decrease in its initial flux of nearly 27% during filtration of contaminants. This irreversible flux loss did not recover after a water wash.
[0136] These experiments demonstrate the improved degree of fouling resistance exhibited by this new membrane family, even with challenging feeds. The minimal membrane flux loss during contaminant filtration can be easily restored by physical cleaning, i.e., rinsing with water. This degree of fouling resistance, with nearly complete retention of membrane flux even during dead-end filtration of highly fouling feeds, is matched only by other ZAC-based membranes and far exceeds the state of the art.
[0137] A rapid thiol-ene click crosslinking strategy was developed to tune the selectivity of the prepared ZAC membranes. This facilitates the relatively rapid fabrication of highly crosslinked ZAC membranes in an efficient scalable manner for roll-to-roll industrial scale-up. This demonstrates that thiol-ene click chemistry can be widely and scalably used to significantly alter the porosity of self-assembled nanofiltration membranes. Increasing UV exposure times between 5 and 14 min showed high rejection of ions and small molecules, with notable changes observed between 0 and 300 s, validating ultrafast kinetics even at shorter time scales. The maximally crosslinked membrane, TERP-C-14, showed exceptional monovalent / divalent selectivity. Meanwhile, the fabricated crosslinked membranes exhibited extraordinary anti-fouling properties necessary for long-term operation. Dead-end filtration of oil / water emulsions or rejection of BSA protein showed no irreversible flux loss. These key findings support the potential use of these highly crosslinked ZAC-based membranes for various industries ranging from water softening, biomolecule separation, textile wastewater treatment, and sulfate removal from seawater for oil drilling, etc. Furthermore, the versatility and functional group tolerance of thiol-ene click chemistry has enabled us to design and fabricate a novel class of crosslinked random zwitterionic copolymer membranes for a wide range of applications.
[0138] INCORPORATION BY REFERENCE All U.S. and PCT patent publications and U.S. patents referred to herein are incorporated herein by reference in their entirety as if each individual patent publication or patent was specifically and individually indicated to be incorporated by reference. In case of conflict, the present application, including any definitions herein, will control.
[0139] Other embodiments Those skilled in the art will recognize or be able to ascertain, using no more than routine experimentation, many equivalents to the specific embodiments described herein. The scope of the embodiments described herein is not intended to be limited to the above description, but is as set forth in the appended claims. Those skilled in the art will appreciate that various changes and modifications to this description can be made without departing from the spirit or scope of the invention, as defined in the following claims.
Claims
1. A crosslinked copolymer network comprising: a copolymer comprising a plurality of zwitterionic repeat units and a plurality of a first type of hydrophobic repeat units; A plurality of cross-linking units; and Multiple crosslinks wherein each crosslinking unit comprises a first terminal thiol moiety and a second terminal thiol moiety, each hydrophobic repeating unit comprises an alkene, and each crosslink is formed from (i) the first terminal thiol moiety of said crosslinking unit and the alkene of said first hydrophobic repeating unit, and (ii) the second terminal thiol moiety of said crosslinking unit and the alkene of said second hydrophobic repeating unit.
2. 10. The crosslinked copolymer network of claim 1, wherein each of said zwitterionic repeat units independently comprises a sulfobetaine, a carboxybetaine, a phosphorylcholine, an imidazolium alkylsulfonate, or a pyridinium alkylsulfonate.
3. each of said zwitterionic repeat units is independently formed from sulfobetaine acrylate, sulfobetaine acrylamide, carboxybetaine acrylate, carboxybetaine methacrylate, 2-methacryloyloxyethyl phosphorylcholine, acryloxyphosphorylcholine, phosphorylcholine acrylamide, phosphorylcholine methacrylamide, carboxybetaine acrylamide, 3-(2-vinylpyridinium-1-yl)propane-1-sulfonate, 3-(4-vinylpyridinium-1-yl)propane-1-sulfonate, or sulfobetaine methacrylate; and / or 10. The crosslinked copolymer network of claim 1, wherein each of said hydrophobic repeat units is independently formed from styrene, alkyl acrylates, alkyl methacrylates, alkyl acrylamides, acrylonitriles, aryl acrylates, aryl methacrylates, and aryl acrylamides.
4. 2. The crosslinked copolymer network of claim 1, wherein the copolymer is poly((allyl methacrylate)-random-(sulfobetaine methacrylate)) or poly((allyl methacrylate)-random-(2-methacryloyloxyethyl phosphorylcholine)), poly((allyl methacrylate)-random-(trifluoroethyl methacrylate)-random-(sulfobetaine methacrylate)) or poly((allyl methacrylate)-random-(trifluoroethyl methacrylate)-random-(2-methacryloyloxyethyl phosphorylcholine)).
5. 2. The crosslinked copolymer network of claim 1, further comprising a plurality of second type hydrophobic repeat units, said second type hydrophobic repeat units each independently formed from an alkyl acrylate, an alkyl methacrylate, an alkyl acrylamide, an acrylonitrile, an aryl acrylate, an aryl methacrylate, and an aryl acrylamide.
6. The crosslinked copolymer network of claim 5, wherein said second type of hydrophobic repeat unit is formed from 2,2,2-trifluoroethyl methacrylate.
7. 7. The crosslinked copolymer network of claim 6, wherein the copolymer is poly(allyl methacrylate-random-trifluoroethyl methacrylate-random-2-methacryloyloxyethyl phosphorylcholine).
8. The crosslinked copolymer network of claim 1, wherein the copolymer has a molecular weight of from about 3,000 to about 10,000,000 Daltons.
9. The crosslinked copolymer network of claim 1 , wherein said zwitterionic repeat units and said hydrophobic repeat units each comprise from 20 to 80 weight percent of the copolymer.
10. 2. The crosslinked copolymer network of claim 1, wherein said copolymer is poly((allyl methacrylate)-random-(sulfobetaine methacrylate), said zwitterionic repeat units constitute 25-75 weight percent of the copolymer, and said copolymer has a molecular weight of about 20,000 to about 100,000 Daltons.
11. The multiple bridging units are represented as FG-CL-FG, where FG is a linker-thiol moiety and CL is C 1 ~C 20 Divalent aliphatic radical, C 1 ~C 20 2. The crosslinked copolymer network of claim 1, wherein the radical is a divalent heteroaliphatic radical, a divalent aryl radical, or a divalent heteroaryl radical.
12. CL is C 1 ~C 20 Divalent aliphatic radical or C 1 ~C 20 12. The crosslinked copolymer network of claim 11, which is a divalent heteroaliphatic radical.
13. FG-CL-FG is -S-(CH 2 ) 6 -S-, or -S-(CH 2 ) 2 -O-(CH 2 ) 2 -O-(CH 2 ) 2 The crosslinked copolymer network of claim 11, wherein the aryl group is -S-.
14. 13. A thin film composite membrane comprising a porous substrate and a selective layer comprising the crosslinked copolymer network of claim 1, wherein the average effective pore size of the porous substrate is larger than the average effective pore size of the selective layer, and the selective layer is disposed on a surface of the porous substrate.
15. the selective layer has an average effective pore size of about 0.1 nm to about 2.0 nm; and / or The thin film composite membrane of claim 14, wherein the selective layer has a thickness of about 10 nm to about 10 μm.
16. 15. The thin film composite membrane of claim 14, wherein the thin film composite membrane rejects charged solutes and salts.
17. The selective layer is made of more than 95% sulfate (SO 4 2- ) blocking rate, and / or the selective layer exhibits a chloride (Cl − ) rejection of less than 35%; and / or 17. The thin film composite membrane of claim 16, wherein the selective layer exhibits a sulfate (SO 4 2− ) / chloride (Cl − ) separation factor of greater than 50.
18. the selective layers exhibit different anion rejections for salts having the same cation, and / or the selective layer exhibits different rejections for different anionic dyes, and / or the selective layer exhibits size-based selectivity between uncharged organic molecules; 15. The thin film composite membrane of claim 14.
19. The selective layer is made of NaF, NaCl, NaBr, NaI, Na 2 SO 4 , and NaClO 4 or the selective layer exhibits a Chicago Sky Blue 6B / Methyl Orange separation factor of about 10; or the selective layer exhibits greater than about 95% vitamin B12 rejection; or the selective layer exhibits a riboflavin rejection rate of greater than about 35%, or The selective layer exhibits a rejection rate of >95% or >99% for neutral molecules having a hydrated diameter of about 1.5 nm or more.
15. The thin film composite membrane of claim 14.
20. The thin film composite membrane of claim 14 , wherein the selective layer exhibits anti-fouling properties.
21. the selective layer exhibits resistance to fouling by oil emulsions; or 21. The thin film composite membrane of claim 20, wherein the selective layer exhibits resistance to fouling by bovine serum albumin solutions.
22. 15. The thin film composite membrane of claim 14, wherein the selective layer is stable when exposed to chlorine bleach.
23. 10. A method for making the crosslinked copolymer network of claim 1, comprising: providing a copolymer comprising a plurality of zwitterionic repeat units and a plurality of a first type of hydrophobic repeat units, each hydrophobic repeat unit comprising an alkene; providing a plurality of bridging units, each bridging unit comprising a first terminal thiol moiety and a second terminal thiol moiety; Providing a photoinitiator; mixing the copolymer, the plurality of crosslinking units, and the photoinitiator, thereby forming a mixture; and irradiating the mixture with UV light, thereby forming a cross-linked copolymer. The method includes:
24. The method of claim 23 , wherein the mixture further comprises a solvent.
25. 25. The method of claim 24, wherein the solvent is a mixture of isopropanol and hexane.
26. The method of any one of claims 23 to 25, wherein the irradiation is performed at room temperature for about 10 seconds to about 20 minutes.
27. The method of any one of claims 23 to 25, wherein the photoinitiator is 2-phenylacetophenone.
28. A method for producing a pharmaceutical product, comprising: Contacting the thin film composite membrane of any one of claims 14 to 22 with a mixture comprising one or more pharmaceutical compounds; and Separating one or more pharmaceutical compounds via size-selective filtration A method comprising:
29. A method for dyeing and finishing textiles comprising the steps of: contacting the thin film composite membrane of any one of claims 14 to 22 with a mixture comprising one or more textile dyes; and Separating one or more textile dyes via size-selective filtration The method includes:
30. 1. A method of buffer exchange comprising the steps of: Contacting the thin film composite membrane of any one of claims 14 to 22 with a first buffer solution; and replacing said first buffer solution with a second buffer solution. The method includes:
31. 1. A method for purifying a peptide, comprising: Contacting the thin film composite membrane of any one of claims 14 to 22 with a mixture comprising one or more peptides; and Separating one or more peptides via size-selective filtration The method includes:
32. 1. A method for removing divalent ions from water, comprising the steps of: Contacting the thin film composite membrane of any one of claims 14 to 22 with an aqueous mixture containing divalent ions; and removing some or all of the divalent ions from said aqueous mixture via size selective filtration; The method includes:
33. 1. A method for removing organic solutes from water, comprising the steps of: Contacting the thin film composite membrane of any one of claims 14 to 22 with an aqueous solution containing an organic solute; and Separating organic solutes via size-selective filtration The method includes:
34. 1. A method for eliminating pathogenic microorganisms, comprising: Contacting the thin film composite membrane of any one of claims 14 to 22 with a mixture comprising one or more pathogenic microorganisms; and Separating one or more pathogenic microorganisms via reverse osmosis The method includes:
35. 1. A method for size selective separation comprising the steps of: Contacting the thin film composite membrane of any one of claims 14 to 22 with a mixture comprising one or more particles of different sizes; and Separating one or more particles via size selective filtration The method includes:
36. 1. A method for processing a food product, comprising: contacting the thin film composite membrane of any one of claims 14 to 22 with an impure food ingredient; and Separating contaminants from said impure food ingredients via size selective filtration. The method includes:
37. 1. A printing method comprising: Contacting the thin film composite film of any one of claims 14 to 22 with one or more inks; and applying said ink or inks to a surface of an article; The method includes: